Compositions and methods for making porous structures having high surface area

By developing a porous structure with high porosity and high specific surface area, the problem of low carbon dioxide capture efficiency in the existing technology is solved, and efficient and economical carbon dioxide capture is achieved.

CN119330602APending Publication Date: 2025-01-21CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310892569.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively capture and utilize carbon dioxide, especially the problem of increasing carbon dioxide concentration in the atmosphere.

Method used

A porous structure containing 5% to 95% hollow glass bodies and 5% to 95% secondary phases was developed, and the hollow glass bodies were sintered and broken to form a honeycomb-shaped porous structure with high porosity and high specific surface area for direct adsorption. carbon dioxide.

Benefits of technology

Efficient carbon dioxide capture is achieved, and the porous structure has a porosity greater than or equal to 50% and a specific surface area greater than or equal to 5m2/g, reducing the cost and energy consumption of the carbon dioxide capture system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330602A_ABST
    Figure CN119330602A_ABST
Patent Text Reader

Abstract

The present application relates to compositions and methods for making porous structures having a high surface area. The porous structure includes from 5% to 95% by weight of a hollow glass body and from 5% to 95% by weight of a secondary phase, based on the total weight of the porous structure. The hollow glass body includes silica-containing glass. The hollow glass body and the secondary phase are sintered together, and at least a portion of the hollow glass body breaks apart. The voids defined within the individual ruptured hollow glass are open to each other to form a cavity that extends through the porous structure and up to an outer surface thereof. The porous structure has a porosity (by volume) of greater than or equal to 50% and may have a specific surface area of greater than or equal to 5 m2 / g. The porous structure can be integrated into a CO2 capture process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to porous structures and, more particularly, to honeycomb shaped porous structures useful as substrates for carbon dioxide capture systems and processes. Background Art

[0002] Since the Industrial Revolution, the amount of carbon dioxide (CO2) in the Earth's atmosphere has steadily increased due to the combustion of fossil fuels such as coal-fired power plants and gasoline / diesel-based vehicles. Such CO2 increases have caused global warming issues and prompted international efforts to control CO2 emissions and / or capture CO2 from the atmosphere to reduce CO2 accumulation in the environment. One solution for CO2 capture is to capture CO2 directly from the air or from point sources such as power plants using solid adsorbents. Ceramic porous structures (e.g., porous ceramic honeycombs) are considered potential carriers for adsorbents used in CO2 capture applications. Summary of the invention

[0003] According to the first aspect disclosed herein, the porous structure may include: 5 wt% to 95 wt% of a hollow glass body, based on the total weight of the porous structure; and 5 wt% to 95 wt% of a secondary phase, based on the total weight of the porous structure. The hollow glass body may include silica-containing glass. The hollow glass body and the secondary phase are sintered together, and at least a portion of the hollow glass body is broken. The cavities defined in the individual broken hollow glass bodies are open to each other to form a cavity that extends through the porous structure and reaches its outer surface. The porous structure may have a porosity greater than or equal to 50% (by volume) and may have a volume greater than or equal to 5m 2 / g specific surface area.

[0004] The second aspect disclosed herein may include the first aspect, wherein the specific surface area of ​​the porous structure may be greater than or equal to 10 m 2 / g or even greater than or equal to 20m 2 / g.

[0005] A third aspect disclosed herein may include any one of the first or second aspects, wherein the porosity of the porous structure may be greater than or equal to 55% or even greater than or equal to 60%.

[0006] A fourth aspect disclosed herein may include any one of aspects 1 to 3, wherein the secondary phase may include: a specific surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles; nano-sized grains comprising a reaction product of a reaction between silica-containing glass and coarse inorganic particles, wherein the coarse inorganic particles have a particle size of less than 10 m 2 / g specific surface area and containing an oxide, hydroxide, salt or a combination thereof of an alkali metal or an alkaline earth metal; or a combination thereof.

[0007] A fifth aspect disclosed herein may include the fourth aspect, wherein the secondary phase may include a surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles.

[0008] A sixth aspect disclosed herein may include the fifth aspect, wherein the nano-sized inorganic particles may have a diameter greater than or equal to 20 m 2 / g, greater than or equal to 50m 2 / g or even greater than or equal to 100m 2 / g specific surface area.

[0009] A seventh aspect disclosed herein may include any one of the fifth or sixth aspects, wherein the nanosized inorganic particles may have a median particle size (d50) of 0.1 nm to 100 nm.

[0010] The eighth aspect disclosed herein may include any one of aspects 5 to 7, wherein the nano-sized inorganic particles may include: gamma alumina, zirconia, zeolite, magnesia, silica, CeO2, TiO2, or a combination thereof.

[0011] A ninth aspect disclosed herein may include any one of aspects 5 to 8, wherein the nano-sized inorganic particles may include gamma alumina.

[0012] A tenth aspect disclosed herein may include any one of aspects 4 to 9, wherein the secondary phase may include nano-sized grains comprising a reaction product of a reaction between the silica-containing glass and the coarse inorganic particles.

[0013] The 11th aspect disclosed herein may include the 10th aspect, wherein the coarse inorganic particles may have a particle size of less than 10 μm. 2 / g specific surface area.

[0014] A 12th aspect disclosed herein may include any one of the 10th or 11th aspects, wherein the coarse inorganic particles may have an average particle size of about 100 nanometers to about 100 micrometers.

[0015] The 13th aspect disclosed herein may include any one of aspects 10 to 12, wherein the coarse inorganic particles may include: MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li2BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or any combination thereof.

[0016] A 14th aspect disclosed herein may include any one of aspects 10 to 13, wherein the coarse inorganic particles may include MgO.

[0017] The 15th aspect disclosed herein may include any one of aspects 10 to 14, wherein the secondary phase may include: at least one magnesium-based crystalline phase selected from forsterite, clinopyroxene, diopside or a combination thereof; at least one calcium-based crystalline phase selected from wollastonite, pseudowollastonite, kilchoanite, crostobalite; or a combination thereof.

[0018] A 16th aspect disclosed herein may include the 4th aspect, wherein the secondary phase may include: a specific surface area greater than or equal to 10m 2 / g of nano-sized inorganic particles and nano-sized crystallites (which include the reaction product between the silica-containing glass and the coarse inorganic particles, the coarse inorganic particles having a size of less than 10 m 2 / g specific surface area and contains an oxide, hydroxide, salt or a combination thereof of an alkali metal or an alkaline earth metal).

[0019] A seventeenth aspect disclosed herein may include the sixteenth aspect, wherein the porous structure may include one or more crystalline phases selected from roedderite, corundum, zirconia, or combinations thereof.

[0020] An eighteenth aspect disclosed herein may include any one of aspects 1 to 17, wherein the porous structure may include a glass phase.

[0021] Aspect 19 disclosed herein may include any one of aspects 1 to 18, wherein the plurality of hollow glass bodies may include borosilicate glass, soda-lime silicate glass, aluminosilicate glass, alkali aluminosilicate glass, or a combination thereof.

[0022] A 20th aspect disclosed herein may include any one of aspects 1 to 19, wherein the porous structure may have a D factor greater than or equal to 0.5, wherein the D factor is equal to (d 50 -d 10 ) / d 50 , d 50 refers to the median pore size of the porous structure when 50% by volume of the open porosity of the porous structure is invaded by mercury during the porosity measurement, and d 10 Equivalent to the pore diameter of the porous structure at which 90 volume % of the open porosity of the porous structure is invaded by mercury during the porosity measurement.

[0023] A 21st aspect disclosed herein may include any one of aspects 1 to 20, wherein the porous structure may have a median pore size of 1 μm to 50 μm or 2 μm to 20 μm.

[0024] Aspect 22 disclosed herein may include any one of aspects 1 to 21, wherein the porous structure may have a honeycomb shape comprising a plurality of elongated channels extending through at least a portion of the porous structure, wherein the porous structure may have a pore density of less than 400 channels per inch and a mesh thickness of between 2 mils and 8 mils, wherein the pore density refers to the number of elongated channels per square inch of the porous structure cross-section.

[0025] Aspect 23 disclosed herein may include any one of aspects 1 to 22, wherein the porous structure may include a size and shape that is within 15% of the size and shape of the extruded green structure before firing to transform the extruded green structure into the porous structure.

[0026] A 24th aspect disclosed herein may include any one of aspects 1 to 23, further comprising one or more CO2 adsorbents deposited within the cavities of the porous structure.

[0027] The 25th aspect disclosed herein may include the 24th aspect, wherein the CO2 adsorbent may include: PEI, MEA, DEA, PPI, PPA, NaOH, Na2CO3, NaHCO3, KOH, K2CO3, KHCO3, or a combination thereof.

[0028] A 26th aspect disclosed herein may include any of the 24th or 25th aspects, wherein the CO2 sorbent may be bonded to a surface of the porous structure defining the cavity.

[0029] A 27th aspect disclosed herein may include any one of aspects 24 to 26, wherein the porous structure does not have an intermediate layer disposed between a surface of the porous structure and the CO 2 sorbent bonded thereto.

[0030] Aspect 28 disclosed herein may include any one of aspects 24 to 28, comprising a CO2 capture process comprising a porous structure of any one of aspects 24 to 28, wherein the CO2 capture process may also include an adsorption-desorption unit and the porous structure may be integrated into the adsorption-desorption unit.

[0031] A 29th aspect disclosed herein may relate to a composition for making a ceramic honeycomb. The composition may include a plurality of hollow glass bodies (including silica-containing glass), a secondary phase precursor, a liquid carrier, and an organic system. The secondary phase precursor may include: a specific surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles; coarse inorganic particles having a particle size of less than 10m 2 / g specific surface area and comprises an oxide, hydroxide, salt or a combination thereof of an alkali metal or an alkaline earth metal; or a combination thereof.

[0032] The 30th aspect disclosed herein may include the 29th aspect, comprising 50 volume % to 95 volume % of the hollow glass body and 5 volume % to 50 volume % of the secondary phase, wherein the volume percentages are based on the total bulk volume of the inorganic solid components of the composition.

[0033] Aspect 31 disclosed herein may include any one of aspects 29 or to 30, wherein the silica-containing glass may include borosilicate glass, soda-lime silicate glass, aluminosilicate glass, alkali aluminosilicate glass, or a combination thereof.

[0034] A 32nd aspect disclosed herein may include any one of aspects 29 to 31, wherein the secondary phase precursor may include nano-sized inorganic particles.

[0035] The 33rd aspect disclosed herein may include the 32nd aspect, wherein the nano-sized inorganic particles may have a diameter greater than or equal to 10 m 2 / g specific surface area.

[0036] A 34th aspect disclosed herein may include any one of the 32nd or 33rd aspects, wherein the nano-sized inorganic particles may include: gamma alumina, zirconia, zeolite, magnesia, silica, CeO2, TiO2, or a combination thereof.

[0037] A 35th aspect disclosed herein may include any one of aspects 29 to 31, wherein the secondary phase precursor may include coarse inorganic particles comprising an oxide, hydroxide, salt, or combination thereof of an alkali metal or an alkaline earth metal.

[0038] The 36th aspect disclosed herein may include the 35th aspect, wherein the coarse inorganic particles may include: MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li3BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or a combination thereof.

[0039] Aspect 37 disclosed herein may include any one of aspects 29 to 36, wherein the inorganic system may include one or more of: methyl cellulose, CMC, a lubricant, PVP, PVA, or a combination thereof.

[0040] A 38th aspect disclosed herein may include any one of aspects 29 to 37, wherein the liquid carrier may be water, one or more alcohols, or a combination thereof.

[0041] A 39th aspect disclosed herein may include any one of aspects 29 to 38, comprising a porous structure prepared from the composition of any one of aspects 29 to 38.

[0042] A 40th aspect disclosed herein may include any one of aspects 29 to 38, and may relate to a porous structure prepared by the following process, which may include: preparing a composition of any one of aspects 29 to 38; forming a green structure from the composition; and firing the green structure at a temperature of less than or equal to 1000° C. or even less than or equal to 900° C. The porous structure may have a porosity greater than or equal to 50% and a porosity greater than or equal to 5 m 2 / g specific surface area.

[0043] A 41st aspect disclosed herein may include the 40th aspect, wherein the porous structure has a size and structure that is within 15% or even within 1% of the size and shape of the green structure before firing.

[0044] A 42nd aspect disclosed herein may include any of the 40th or 41st aspects, wherein the secondary phase precursor may include nanosized inorganic particles, and firing the green structure may bond the hollow glass microspheres and the nanosized inorganic particles together and may fracture at least a portion of the hollow glass body to form a porous structure, wherein the porous structure has a porosity greater than or equal to 50% and a void volume greater than or equal to 5 m 2 / g specific surface area.

[0045] A 43rd aspect disclosed herein may include any one of aspects 40 to 42, wherein the secondary phase precursor may include coarse inorganic particles comprising an oxide, hydroxide, salt or combination thereof of an alkali metal or an alkaline earth metal, and firing the green structure may result in a reaction between the silica-containing glass of the hollow glass body to produce nano-sized grains and may fracture at least a portion of the hollow glass body to form a porous structure having a porosity greater than or equal to 50% and a void volume greater than or equal to 5 m 2 / g specific surface area.

[0046] Aspect 44 of the present disclosure may include any one of aspects 40 to 43, wherein firing the green structure may include: heating the green structure to a peak firing temperature less than or equal to 1000°C, and maintaining the green structure at the peak firing temperature for a period of 1 hour to 10 hours.

[0047] A 45th aspect disclosed herein may include any one of aspects 40 to 44, wherein the porous structure may further include a CO2 adsorbent bonded to a surface of a cavity of the porous structure, and the process may further include bonding the CO2 adsorbent to the porous structure.

[0048] A 46th aspect disclosed herein may include any one of aspects 40 to 45, wherein bonding the CO 2 sorbent to the porous structure does not include applying an intermediate layer between a surface of the porous structure and the CO 2 sorbent.

[0049] Other features and advantages of the subject matter described and claimed herein are set forth in the following detailed description, some of which will be readily apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.

[0050] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overall review or framework for understanding the nature and characteristics of the claimed subject matter. The included drawings provide a further understanding of the various embodiments, and the drawings are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 schematically shows a front perspective view of a porous structure according to one or more embodiments shown and described herein;

[0052] Figure 2 schematically showing a perspective view of another porous structure according to one or more embodiments shown and described herein;

[0053] Figure 3 schematically showing a cross-sectional view of a carbon capture device comprising a porous structure having a carbon dioxide adsorbent according to one or more embodiments shown and described herein;

[0054] Figure 4 schematically illustrates one embodiment of a carbon dioxide capture system comprising a porous structure of the present disclosure according to one or more embodiments shown and described herein;

[0055] Figure 5A , 5B , 5C, 5D and 5E are scanning electron microscope (SEM) images showing the surface morphology of porous structures made of hollow glass microspheres and gamma alumina (γ-Al2O3) particles and fired at different firing temperatures according to one or more embodiments shown and described herein;

[0056] Figure 6 A schematic diagram of a device according to one or more embodiments shown and described herein Figures 5A-5E X-ray diffraction (XRD) pattern of the porous structure;

[0057] Figure 7 A schematic diagram of a device according to one or more embodiments shown and described herein Figures 5A-5E The pore size distribution of the porous structure;

[0058] Fig. 8A , 8B , 8C and 8D are SEM images showing the surface morphology of porous structures made of hollow glass microspheres and magnesium oxide (MgO) particles and fired at different firing temperatures according to one or more embodiments shown and described herein;

[0059] Fig.9A , 9B , 9C and 9D are respectively according to one or more embodiments shown and described herein Fig. 8A , 8B , SEM images of the porous structures of 8C and 8D (taken at higher resolution);

[0060] Fig.10 graphically showing XRD patterns of porous structures prepared from a composition comprising hollow glass microspheres and MgO particles and fired at different firing temperatures according to one or more embodiments shown and described herein;

[0061] Fig.11 A schematic diagram of a device according to one or more embodiments shown and described herein Fig. 8A , 8B , pore size distribution of the porous structures of 8C and 8D;

[0062] Fig. 12A , 12B , 12C and 12D are SEM images showing the surface morphology of a porous structure made from a composition comprising hollow glass microspheres, 20 volume % MgO particles, and 15 volume % gamma alumina particles and fired at different firing temperatures according to one or more embodiments shown and described herein;

[0063] Fig.13A , 13B, 13C and 13D are respectively according to one or more embodiments shown and described herein Fig. 12A , 12B , SEM images of the porous structures of 12C and 12D (taken at higher resolution);

[0064] Fig.14A , 14B , 14C and 14D are SEM images showing the surface morphology of a porous structure made from a composition comprising hollow glass microspheres, 10 volume % MgO particles, and 10 volume % gamma alumina particles and fired at different firing temperatures according to one or more embodiments shown and described herein;

[0065] Fig.15A , 15B , 15C and 15D are respectively according to one or more embodiments shown and described herein Fig.14A , 14B , SEM images of the porous structures of 14C and 14D (taken at higher resolution);

[0066] Fig.16 A schematic diagram of a device according to one or more embodiments shown and described herein Fig. 12A , 12B , 12C and 12D; and

[0067] Fig.17 A schematic diagram of a device according to one or more embodiments shown and described herein Fig.14A , 14B , 14C and 14D. DETAILED DESCRIPTION

[0068] Reference will now be made specifically to various embodiments of the porous structures disclosed herein, batch compositions for making the porous structures, CO2 capture devices and methods incorporating the porous structures. Whenever possible, the same reference numerals are used in the accompanying drawings to represent the same or similar parts. The present disclosure relates to a honeycomb-shaped porous structure with high porosity and high specific surface area. The porous structure contains 5% to 95% by weight of a hollow glass body, based on the total weight of the porous structure, the hollow glass body containing silica glass. The porous structure also contains 5% to 95% by weight of a secondary phase, based on the total weight of the porous structure. The hollow glass body and the secondary phase are sintered together, and at least a portion of the hollow glass body is broken. The cavities defined in the individual broken hollow glass bodies are open to each other to form a cavity, which extends through the porous structure and reaches its outer surface. The porous structure can have a porosity greater than or equal to 50% (by volume) and a volume greater than or equal to 5m 2 / g specific surface area.

[0069] The porous structure disclosed herein has a thickness greater than or equal to 5 m 2 / g of high specific surface area and high porosity (for example, greater than or equal to 50% porosity). In addition, after firing, the porous structure may have a composition that includes constituent components loaded on the porous structure that can enhance the performance of the alkaline adsorbent, such as but not limited to: PEI, MEA, DEA, PPI, PPA, etc. One or more of the crystalline phases formed during the firing of the porous structure can enhance the performance of the adsorbent loaded thereon. In addition, the composition of the ceramic honeycomb disclosed herein may have a low firing temperature, such as a peak firing temperature of less than about 1000°C, less than about 950°C, or even less than or equal to 900°C. In comparison, conventional cordierite honeycombs are fired at temperatures greater than about 1400°C. The porous structure can be used as a substrate for CO2 capture applications. The porous structure is greater than or equal to 5m 2 The high specific surface area of ​​1.347 W / g enables the carbon dioxide adsorbent to be applied directly to the surface of the porous structure without first applying an intermediate layer.

[0070] As used herein, the term "hollow body" refers to a particle that includes a shell made of glass and surrounding an interior volume that contains a substance other than glass (eg, air or other gas).

[0071] As used herein, the term "green structure" refers to a structure formed from a composition disclosed herein that has not yet been fired.

[0072] As used herein, the term "peak firing temperature" refers to the maximum temperature during the firing process at which the green structure is maintained for a period of time before gradually cooling to ambient temperature.

[0073] As used herein, the term "dwell" or "dwell period" may refer to one or more periods of time during a firing process during which the temperature of a green structure is maintained relatively constant, such as maintaining the temperature of the green structure within a specified range relative to a target temperature.

[0074] As used herein, the term "lower crystallization temperature" of a composition (eg, a glass composition) may refer to a temperature at which one or more constituent components of the composition begin to devitrify and / or crystallize.

[0075] As used herein, the term "upper crystallization temperature" of a composition (eg, a glass composition) may refer to a temperature at which devitrification is significantly slowed and crystallization occurs at an insignificant rate.

[0076] As used herein, the term "crystallization temperature zone" refers to a temperature range between the lower temperature of the crystallization zone and the lower temperature of the crystallization zone.

[0077] As used herein, the term "cell density" refers to the number of elongated channels of a honeycomb porous structure per unit of cross-sectional area of ​​the honeycomb porous structure and is given in cells per square inch. A cell refers to the cross-section of a single elongated channel.

[0078] As discussed above, the capture of CO2 from the atmosphere is gaining attention due to the increasing concentration of CO2 in the Earth's atmosphere. The CO2 capture process involves the adsorption of CO2 from the air or from a point source (e.g., a combustion gas exhaust) using one or more CO2 adsorbents. These adsorbents can be applied to a substrate. Ceramic porous structures (e.g., porous ceramic honeycombs) are considered as potential carrier substrates for adsorbents for these CO2 capture applications. Over the past few decades, ceramic honeycombs have been developed and integrated into engine aftertreatment systems to capture fine particles from diesel and gasoline engine exhaust or to decompose SO2, NO x . Compared to other types of substrates, ceramic honeycombs offer: reduced pressure drop, lower energy consumption during the service life of the filter, the ability to regenerate, longer service life, reduced solid waste, and lower cost of ownership over the entire life cycle. Honeycombs used for engine aftertreatment are based on ceramics (e.g., cordierite, AT, SiC, etc.) and have been processed to withstand high temperatures (e.g., 800°C or higher) and high thermal shock. Such properties are not necessary for CO2 capture from ambient air or point sources (e.g., fuel gas). In addition, ceramic honeycombs typically constructed from cordierite usually have a diameter of less than 1 m 2 / g or even less than 0.5m 2 / g low specific surface area. In order to provide sufficient surface area for CO2 capture, the ceramic honeycomb with a low specific surface area must first be processed to apply an intermediate layer to the surface of the ceramic honeycomb to increase the surface area. Then, the adsorbent for CO2 capture is applied to the intermediate layer. The intermediate layer requires additional materials and additional process steps to produce a CO2 capture device.

[0079] There is a continuing need for such a honeycomb-shaped porous structure, which has properties and performance suitable for use as a honeycomb-shaped substrate for CO2 capture devices and processes and provides cost-effectiveness. The present application relates to a honeycomb-shaped porous structure having a high porosity greater than or equal to 50% by volume and a high specific surface area (e.g., greater than or equal to 5 m 2 / g) of porous structure. The porous structure disclosed herein includes a hollow glass body and a secondary phase with a high surface area. Tiny hollow glass bodies (also referred to as glass bubbles, microspheres or hollow glass "microspheres") are commercially available from, for example, Dennert Poraver, 3M, Zhongke Yali Technology Co., Ltd., Fibre Glast Developments Corp, and Potters Industries LLC. The hollow glass bodies can be arranged and processed to produce a particularly efficient porous structure with open porosity, which can be used as a honeycomb-shaped substrate for an adsorption / desorption unit in a CO2 capture process. The structure with open porosity can be formed by packing the hollow bodies tightly together so that the hollow bodies are bonded to each other, and also by rupturing the hollow bodies (e.g., breaking, bursting, shattering, opening, exposing their hollow cores) to create cavities in the porous structure. These cavities of the individual hollow glass bodies can open to each other to form porous cavities that extend throughout the porous structure and are interconnected and can be accessible to its surface. The porous structures disclosed herein can be provided with a high surface area by a secondary phase, which can include: a surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles; nano-sized crystals comprising silica glass with a surface area of ​​less than 10m 2 / g of coarse inorganic particles; or a combination of these.

[0080] The present disclosure also relates to a batch composition for making a porous structure. The batch composition for making a porous structure may include at least a hollow glass body and a secondary phase precursor. The secondary phase precursor may be: a material having a surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles with a surface area of ​​less than 10m 2 / g of coarse inorganic particles, or a combination of the two. The coarse inorganic particles can be oxides, hydroxides, salts or combinations thereof of alkali metals and / or alkaline earth metals, and can be reactive with the glass of the hollow glass body at a temperature of 800°C to 1000°C to form nano-sized grains with a high surface area. The present disclosure also relates to a CO2 capture device comprising a porous structure disclosed herein and one or more adsorbents applied to the surface of the porous structure.

[0081] The porous structure disclosed herein has a thickness greater than or equal to 5 m 2 / g of high surface area and high porosity (e.g., greater than or equal to 50% porosity). In addition, after firing, the porous structure may have a composition that includes constituent components loaded on the porous structure that can enhance the performance of the alkaline adsorbent, such as but not limited to: PEI, MEA, DEA, PPI, PPA, etc. Specifically, the composition of the porous structure may include at least one magnesium-based crystalline phase, such as but not limited to: forsterite, clinopyroxene and / or diopside. In addition or alternatively, in an embodiment, the composition of the porous structure may also include one or more calcium-based crystalline phases, such as but not limited to: wollastonite, pseudowollastonite, kilchoanite, crostobalite, or a combination of these. In addition or alternatively, in an embodiment, the composition of the porous structure may also include one or more of the following: roedderite, corundum, zirconia and glass. One or more of these phases in the composition of the porous structure can enhance the performance of the adsorbent loaded thereon. Without intending to be limited to any particular theory, it is believed that the porous structure is greater than or equal to 5m 2 The high surface area of ​​1000 g / g can promote better adsorbent distribution, which can increase the accessibility of CO2 to the adsorbent, thereby increasing the adsorption performance. In addition, the composition of the honeycomb-shaped porous structure disclosed herein can have a low firing temperature, such as a peak firing temperature of less than about 1000°C, less than about 950°C, or even less than about 900°C, compared to conventional cordierite honeycombs fired at temperatures greater than about 1400°C.

[0082] The porous structure can be used as a substrate for CO2 capture applications. The porous structure is greater than or equal to 5m 2 The high specific surface area of ​​2.174 W / g makes it possible to apply the carbon dioxide adsorbent directly to the surface of the porous structure without first applying an intermediate layer.

[0083] See now Figure 1, schematically showing one embodiment of a porous structure 112 disclosed herein that includes a ceramic honeycomb. The porous structure 112 may be "honeycomb" in that the porous structure 112 may include elongated channels 212 that generally extend through at least a portion of the porous structure 112, such as linearly extending from an outer surface 214 (e.g., a face) of the porous structure 112 to or near an opposite outer surface of the porous structure 112. In an embodiment, some or all of the elongated channels 212 may be open at both ends, which may allow a fluid (e.g., a gas containing CO2, a desorbed gas, etc.) to flow through the elongated channels 212. In an embodiment, the porous structure 112 may include a plug (not shown) at the end of one or more elongated channels, wherein the plug forces the fluid to flow through the walls and network of the porous structure. The plug may force the fluid from one channel to flow through the pores in the wall of the porous structure and into another adjacent channel. The flow of the fluid through the pores of the porous structure may provide a greater degree of contact between the fluid (e.g., a gas containing CO2) and the adsorbent contained in the pores of the porous structure. In other embodiments, the porous structure 112 may be porous but not include the elongated channels 212 such that the CO 2 -containing gas passes through the pores of the porous structure.

[0084] See again Figure 1 When present, the elongated channel 212 can have a high aspect ratio (e.g., length-to-width ratio or length-to-diameter ratio), wherein the length L is oriented along (i.e., parallel to) the flow path of the elongated channel 212 between openings of the elongated channel 212 provided on the outer surface 214 of the porous structure 112, as shown in FIG. Figure 1 As shown. The elongated channels 212 are elongated such that the aspect ratio (defined as the relationship between the length of the elongated channels 212 and the widest cross-sectional dimension of the corresponding elongated channels 212 perpendicular to the length L of at least some (e.g., most, >90%, all) of the channels (e.g., L divided by the channel diameter for channels with circular cross-sections)) is: greater than or equal to 10, greater than or equal to 20, greater than or equal to 50, greater than or equal to 100, and less than or equal to 50,000. The elongated channels 212 can have any conventional cross-sectional shape, such as: Figure 1 The square shown, Figure 3 Circular as shown, or any other convenient shape.

[0085] See now Figure 2 In an embodiment, the porous structure 112 may have a square or rectangular cross-sectional shape instead of Figure 1 The circular cross-sectional shape shown. Figure 1 and 2The porous structure 112 is shown having a generally cylindrical geometry, but other geometries are contemplated, such as cubes, cuboids, sheets, or more complex geometries. According to embodiments, the porous structure 112 may be highly porous, and the pores (e.g., cavities, holes, spaces between structures) are open to one another, such that fluids may flow through the pores into and through the porous structure 112. However, in some such embodiments, the porous structure 112 may be only semi-permeable, allowing only some fluids to pass through the porous structure 112, but trapping or blocking others.

[0086] The porous structure can be produced from a batch composition comprising at least a hollow glass body and at least one secondary phase precursor. The batch composition can also include a liquid carrier and an organic system. The organic system can include one or more binders, additives, etc. The batch composition of the present disclosure can be formed into a green structure and then fired to produce a porous structure. The green structure can refer to a pre-fired or pre-sintered structure made from the batch composition before firing and / or sintering. The green structure can be a porous structure (e.g., Figure 1 The honeycomb-shaped porous structure 112 shown has an outer wall and / or inner wall or mesh.

[0087] After the green structure is fired, the porous structure may contain: 5% to 95% by weight of glass, crystallized glass, or both; and 5% to 95% by weight of a secondary phase, based on the total weight of the porous structure. The glass, crystallized glass, or both may include a silica-containing glass composition. The hollow glass body and the secondary phase may be sintered together, and at least a portion of the hollow glass body may be broken open. The cavities defined within the individual broken hollow glass bodies may be open to each other to form a cavity that extends through the porous structure and reaches its outer surface. The porous structure has a porosity greater than or equal to 50% (by volume) and a microporous structure greater than or equal to 5 m 2 / g of surface area.

[0088] In embodiments, the porous structure 112 may contain a significant proportion of glass, crystallized glass, or both, for example, at least 25 weight percent, at least 40 percent, at least 45 percent, at least 50 percent, at least 55 percent, at least 60 percent, at least 65 percent, at least 70 percent, at least 75 percent, at least 80 percent, at least 85 percent, at least 90 percent, or even at least 95 percent, by weight of glass, crystallized glass, or both, based on the total weight of the porous structure. For those in the industry, such a large proportion of the porous structure 112 formed of hollow glass bodies of glass and / or crystallized glass may be surprising or counterintuitive because they may expect such structures to be particularly brittle and / or not held together at all.

[0089] In embodiments, the porous structure 112 may include about 5 wt % to about 95 wt % of the glass from the hollow glass body, based on the total weight of the porous structure 112, for example: about 5 wt % to about 75 wt %, about 5 wt % to about 60 wt %, about 5 wt % to about 55 wt %, about 5 wt % to about 50 wt %, about 5 wt % to about 45 wt %, about 5 wt % to about 40 wt %, about 5 wt % to about 35 wt %, about 5 wt % to about 30 wt %, about 5 wt % to about 25 wt %, about 5 wt % to about 20 wt %, about 10 wt % to about 95 wt %, about 10 wt % to about 75 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 55 wt %, about 10 wt % to about 50 wt %, about 10 wt % to about 45 wt %, about 5 wt % to about 40 wt %, about 10 wt % to about 35 wt %, about 5 wt % to about 30 wt %, about 10 wt % to about 25 wt %, about 10 wt % to about % to about 20 wt %, about 15 wt % to about 95 wt %, about 15 wt % to about 75 wt %, about 15 wt % to about 60 wt %, about 15 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 15 wt % to about 25 wt %, about 15 wt % to about 20 wt %, about 20 wt % to about 95 wt %, about 20 wt % to about 75 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 20 wt % to about 25 wt %, or any subrange therebetween, of glass from the hollow glass body, based on the total weight of the porous structure.

[0090] In embodiments, the porous structure 112 may include from about 5 wt % to about 95 wt % of the secondary phase, based on the total weight of the porous structure 112, for example: from about 5 wt % to about 75 wt %, from about 5 wt % to about 60 wt %, from about 5 wt % to about 55 wt %, from about 5 wt % to about 50 wt %, from about 5 wt % to about 45 wt %, from about 5 wt % to about 40 wt %, from about 5 wt % to about 35 wt %, from about 5 wt % to about 30 wt %, from about 5 wt % to about 25 wt %, from about 5 wt % to about 20 wt %, from about 10 wt % to about 95 wt %, from about 10 wt % to about 75 wt %, from about 10 wt % to about 60 wt %, from about 10 wt % to about 55 wt %, from about 10 wt % to about 50 wt %, from about 10 wt % to about 45 wt %, from about 10 wt % to about 40 wt %, from about 10 wt % to about 35 wt %, from about 5 wt % to about 30 wt %, from about 10 wt % to about 25 wt %, from about 10 wt % to about % to about 20 wt %, about 15 wt % to about 95 wt %, about 15 wt % to about 75 wt %, about 15 wt % to about 60 wt %, about 15 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 15 wt % to about 25 wt %, about 15 wt % to about 20 wt %, about 20 wt % to about 95 wt %, about 20 wt % to about 75 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 20 wt % to about 25 wt %, or any subrange therebetween, based on the total weight of the porous structure.

[0091] In an embodiment, the secondary phase may include a surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles. During the firing process, the nano-sized inorganic particles can remain substantially unchanged and can provide a high surface area structure embedded in the surface of the glass from the hollow glass body. In an embodiment, the secondary phase precursor can be a coarse inorganic particle, and the secondary phase can include a reaction product of a reaction between the silica-containing glass of the hollow glass body and the coarse inorganic particle, wherein the coarse inorganic particle has a particle size of less than 10 m 2 / g surface area and contains oxides, hydroxides, salts or combinations thereof of alkali metals and / or alkaline earth metals. The reaction between the silica-containing glass and the coarse inorganic particles can produce a surface area greater than about 10 m 2 / g of nano-sized grains. The nano-sized grains may include one or more crystalline phases, such as but not limited to: forsterite, clinopyroxene, diopside, wollastonite, pseudowollastonite, orthorhombic calcite, cristobalite, magnesia, corundum, other secondary crystalline phases, or combinations thereof. In an embodiment, the secondary phase may also include nano-sized inorganic particles (having a particle size greater than or equal to 10 m 2 / g surface area) and nano-sized crystallites (which include hollow glass bodies containing silica and a surface area of ​​less than 10 m 2 / g of coarse inorganic particles) the reaction product of the reaction between the two.

[0092] As discussed above, the batch composition disclosed herein for making a porous structure may include at least a plurality of hollow glass bodies and a secondary phase precursor. The hollow glass body may include silica-containing glass. In an embodiment, the batch composition may further include at least one liquid vehicle and an organic system. The organic system may include one or more binders, one or more additives, or a combination of these.

[0093] Batch compositions disclosed herein include hollow glass bodies. Throughout this specification, hollow bodies and hollow glass bodies can be used interchangeably. The batch compositions of the present disclosure and the porous structures manufactured therefrom can include and / or can be at least partially formed by a plurality of hollow glass bodies, wherein "a plurality" of hollow glass bodies can mean greater than or equal to 100 or even greater than or equal to 1,000 hollow glass bodies. The hollow glass bodies can act as both pore formers and primary framework structures, thereby providing high porosity for the porous structure. The hollow glass bodies can include a glass shell enclosing a hollow volume. The hollow volume can contain a gas, such as, but not limited to, air or other gases. The hollow glass bodies can have various shapes. The hollow glass bodies can be roughly spherical or can have an irregular shape, such as a potato shape.

[0094] The hollow glass bodies can be characterized by diameter, wherein "diameter" can refer to the diameter of the hollow body if the volume of the hollow body is arranged in a perfect spherical geometry. The size of the hollow glass bodies can be selected and characterized based on the diameter, wherein the "D50" particle size corresponds to the point where 50% of the hollow glass bodies with a diameter of the D50 value pass through, wherein half of the diameters in the group are greater than the D50 value and half of the diameters are less than the D50 value. The hollow glass bodies can have a D50 greater than or equal to 1 μm, greater than or equal to 3 μm, greater than or equal to 5 μm, or even greater than or equal to 10 μm. The hollow glass bodies can have a D50 less than or equal to 100 μm, less than or equal to 50 μm, or even less than or equal to 40 μm. The hollow glass body can have a D50 of 1 μm to 100 μm, 1 μm to 50 μm, 1 μm to 40 μm, 3 μm to 100 μm, 3 μm to 50 μm, 3 μm to 40 μm, 5 μm to 100 μm, 5 μm to 50 μm, 5 μm to 40 μm, 10 μm to 100 μm, 10 μm to 50 μm, or 10 μm to 40 μm.

[0095] The D10 value of a hollow glass body refers to the 10% through point of the hollow body, wherein only 10% of the hollow bodies have a diameter less than the D10 value. The D90 value of a hollow glass body refers to the 90% through point of the hollow glass body, wherein 90% of the hollow glass bodies have a diameter less than the D90 value. The D10 and D90 values ​​of a hollow glass body can be used to evaluate the particle size distribution of the hollow glass body. The particle size distribution of the hollow glass body can usually be characterized by the expression (D90-D10) / D50. The hollow glass body can have the following particle size distribution: less than or equal to 2, less than or equal to 1.5, less than or equal to 1, less than or equal to 0.8, less than or equal to 0.4, less than or equal to 0.2, less than or equal to 0.1, or less than or equal to 0.06, wherein the particle size distribution is defined by the quotient of (D90-D10) / D50. In an embodiment, the composition may include two or more hollow glass bodies of different types or sizes. In these embodiments, each type or size of hollow glass bodies can be characterized by a D50 value and a particle size distribution, such that the particle size distribution of the hollow glass bodies throughout the composition is multimodal.

[0096] Before incorporation into the composition and prior to firing (i.e., prior to fracture of the hollow glass body, as discussed further herein), the hollow glass body may have a viscosity greater than or equal to about 0.1 g / cm 3 The density is, for example, greater than or equal to about 0.3 g / cm 3 , where density is mass per volume, which includes the internal bubble volume of the hollow glass body. The hollow glass body incorporated into the composition and prior to firing may have a density of less than or equal to about 1.5 g / cm3 Density, for example: less than or equal to about 1.0 g / cm 3 , or even less than or equal to about 0.7 g / cm 3 Before firing, the hollow glass body may have a density of about 0.1 g / cm 3 To about 1.5g / cm 3 , about 0.1g / cm 3 To about 1.0g / cm 3 , about 0.1g / cm 3 To about 0.7g / cm 3 , about 0.3g / cm 3 To about 1.5g / cm 3 , about 0.3g / cm 3 To about 1.0g / cm 3 , or about 0.3g / cm 3 To about 0.7g / cm 3 .

[0097] The hollow glass body can have a shell wall thickness sufficient to enable the hollow glass body to withstand forming into a green structure (e.g., by extrusion or molding), but thin enough to allow a large portion of the hollow glass body to break during firing. The hollow glass body can have an average wall thickness of about 0.2 μm to about 10 μm, or about 1 μm to about 3 μm.

[0098] The isostatic crush strength of the hollow glass body can be sufficient to prevent the hollow glass body from breaking during the forming process (e.g., during extrusion). The isostatic crush strength of the hollow glass body depends on the shell thickness, particle size, and glass composition of the hollow glass body. In embodiments, particularly resilient hollow glass bodies can be used, such as those having a median isostatic crush strength of at least 1000 psi (6.9 MPa), such as at least 2000 psi (13.8 MPa), such as at least 3000 psi (20.7 MPa) (see Yun and Shou, "Measuring Isostatic Pressing Strength of Hollow Glass Microspheres by Mercury-injection Apparatus", Key Engineering Materials, No. 544, pp. 460-5 (2013)).

[0099] The hollow glass body may include glass (e.g., consisting of, consisting essentially of, consisting of by volume). In an embodiment, the hollow glass body may include, consist essentially of, or consist of silica-containing glass, such as, but not limited to, silica glass, soda-lime silicate glass, borosilicate glass, aluminosilicate glass, or other glass. In an embodiment, the hollow body may include, consist essentially of, or consist of silica-containing glass microspheres. The glass of the hollow glass body may be completely amorphous. In an embodiment, the glass of the hollow glass body may be amorphous before heating, and may then devitrify and / or crystallize during the processing process. For clarification, "glass" as used herein includes amorphous glass and / or at least partially devitrified glass having crystals.

[0100] According to embodiments, a hollow glass body having a high crystallinity at the softening temperature of the hollow glass body (e.g., a hollow glass body comprising more than 45 wt. % silicon dioxide (SiO2) and / or CaSiO3, etc.) facilitates the transition process from internal porosity to open interconnected porosity, as discussed below. The glass composition constituent components may include more than 50 wt. % SiO2, for example: 50 wt. % to 85 wt. %, 50 wt. % to 80 wt. %, 74 wt. % to 85 wt. % SiO2, or 74 wt. % to 80 wt. % SiO2, based on the total weight of the glass. In embodiments, the glass of the hollow glass body may additionally include: more than about 6.5% CaO, less than about 7% and at least some B2O3, less than about 1% and at least some Al2O3, at least some Fe2O3, less than 2.5% and at least some Na2O, and / or at least some K2O. In an embodiment, the glass of the hollow glass body may include MgO, such as 0 wt % to 15 wt % MgO. In an embodiment, the glass of the hollow glass body is, is primarily, or includes: soda-lime silicate glass, borosilicate glass, and / or aluminosilicate glass. Some exemplary glass compositions and corresponding properties of various hollow glass bodies are provided in Tables 1 and 2. Hollow glass bodies with different compositions may also be used to have similar effects.

[0101] Table 1: Exemplary Hollow Glass Body Compositions

[0102]

[0103]

[0104] Table 2: Properties of hollow glass bodies

[0105]

[0106] In embodiments, the batch composition may include multiple different types of hollow glass bodies, such as hollow glass bodies having different glass compositions or different physical properties. The different physical properties may include: different median or average particle sizes, different softening temperatures, different particle size distributions, different densities, different shell thicknesses, different crush strengths, or combinations thereof. In embodiments, the batch composition may include a first hollow glass body and a second hollow glass body, wherein the second glass body differs from the first hollow glass body in one or more of the following: glass composition, median or average particle size, softening temperature, particle size distribution, density, shell thickness, crush strength, or combinations thereof.

[0107] The batch composition of the present disclosure may include an amount of hollow glass sufficient to produce a porous structure having a porosity greater than or equal to 50%, greater than or equal to 60%, or even greater than or equal to 70%. In an embodiment, the composition may include 50% to 99% by volume of hollow glass, wherein the volume percentage refers to the true volume of the hollow glass (including the internal volume within the shell) divided by the total true volume of the hollow glass and the secondary phase precursor (e.g., excluding water, binders, or additives). The true volume of the hollow glass refers to the volume of the hollow glass including the shell and the internal volume defined by the shell, but does not include the void spaces between the hollow glass. The true volume of the secondary phase precursor refers to the volume of the particles excluding the inter-particle and intra-particle spaces in the powder. The batch composition can include: about 50 volume % to about 95 volume %, about 50 volume % to about 85 volume %, about 50 volume % to about 75 volume %, about 60 volume % to about 99 volume %, about 60 volume % to about 95 volume %, about 60 volume % to about 90 volume %, about 60 volume % to about 85 volume %, about 60 volume % to about 75 volume %, about 75 volume % to about 99 volume %, or about 75 volume % to about 95 volume % of the hollow glass body, wherein the volume percentage refers to the actual volume of the hollow glass body (including the internal volume within the shell) divided by the total actual volume of the hollow glass body and the actual volume of the secondary phase precursor.

[0108] The batch composition may include about 5% to about 95% by weight of the hollow glass body, wherein the weight percentages are based on the total weight of the hollow glass body and the secondary phase precursor. The batch composition may include: about 5% to about 90% by weight, about 5% to about 80% by weight, about 5% to about 70% by weight, about 25% to about 95% by weight, about 25% to about 90% by weight, about 25% to about 80% by weight, about 25% to about 70% by weight, about 50% to about 90% by weight, about 50% to about 80% by weight, or about 50% to about 70% by weight of the hollow glass body, based on the total weight of the hollow glass body and the secondary phase precursor. In embodiments, the batch composition may include 5% to 95% by weight of the hollow glass body, based on the total weight of the batch composition (e.g., including the liquid vehicle and the organic system in addition to the hollow glass body and the secondary phase precursor), such as: 5% to 90%, 5% to 80%, 5% to 50%, 5% to 40%, 5% to 35%, 10% to 95%, 10% to 90%, 10% to 80%, 10% to 50%, 10% to 40%, 10% to 35%, 20% to 95%, 20% to 90%, 20% to 80%, 20% to 50%, 20% to 40%, or 20% to 35% by weight of the hollow glass body, based on the total weight of the batch composition.

[0109] The secondary phase precursor is a solid inorganic particulate material that is not a glass. In embodiments, the secondary phase precursor may include nano-sized inorganic particles having a high surface area. The melting temperature of the nano-sized inorganic particles may be greater than the softening temperature of the glass of the hollow glass body. The nano-sized inorganic particles may have a diameter greater than or equal to about 10 m 2 In an embodiment, the nano-sized inorganic particles may have a surface area of ​​greater than or equal to about 20 m 2 / g, greater than or equal to about 50m 2 / g, greater than or equal to about 100m 2 / g, greater than or equal to about 150m 2 / g, or even greater than or equal to about 200m 2 In an embodiment, the nano-sized inorganic particles may have a size of about 10 m 2 / g to about 1000m 2 / g surface area, for example: about 10m 2 / g to about 900m 2 / g, about 20m 2 / g to about 1000m 2 / g, about 20m 2 / g to about 900m 2 / g, about 50m 2 / g to about 1000m 2 / g, about 50m 2 / g to about 900m 2 / g, about 100m 2 / g to about 1000m 2 / g, about 150m 2 / g to about 1000m 2 / g, or about 200m 2 / g to about 1000m 2 / g. The range of median particle size of the nano-sized inorganic particles can allow the nano-sized inorganic particles to be distributed on the surface of the glass phase after firing. In an embodiment, the nano-sized inorganic particles can have a median particle size (d50) of about 0.1 nanometers to about 100 nanometers, for example: about 0.5 nanometers to about 100 nanometers, or about 1 nanometer to about 100 nanometers.

[0110] During firing at a temperature less than or equal to the peak firing temperature, the nano-sized inorganic particles can be non-reactive or have very low reactivity relative to the glass of the hollow glass body. Thus, after firing, the nano-sized inorganic particles can remain chemically and physically the same as before they were fired. When the secondary phase precursor is a nano-sized inorganic particle, the nano-sized inorganic particles (in their initial form) can become a secondary phase. The nano-sized inorganic particles can include one or more of the following: gamma alumina (γ-Al2O3), zirconium oxide, zeolite, magnesium oxide, silica, cerium oxide (CeO2), titanium oxide (TiO2), or any combination thereof. In an embodiment, the nano-sized inorganic particles can be selected from the group consisting of gamma alumina, zirconium oxide, zeolite, magnesium oxide, silica, CeO2, TiO2, and any combination thereof. In an embodiment, the nano-sized inorganic particles can include gamma alumina. The nano-sized inorganic particles can act as a rigid frame element, which can reduce the flowability of the softened hollow glass body when heated to a temperature above the softening temperature of the hollow glass body. The nano-sized inorganic particles can be capable of maintaining their initial particle shape at a temperature above the softening temperature of the hollow glass body. In an embodiment, the nano-sized inorganic particles can be capable of maintaining their initial shape at a temperature greater than or equal to 500°C or even greater than or equal to 800°C (e.g., about 500°C to about 1000°C).

[0111] In embodiments, the secondary phase precursor may include coarse inorganic particles having a lower surface area than the nano-sized inorganic particles. The coarse inorganic particles may be reactive with the glass of the hollow glass body during firing to produce nano-sized grains containing one or more secondary crystalline phases and having a high surface area, e.g., greater than 10 m 2 In some embodiments, the coarse inorganic particles may have a surface area of ​​100 μm / g. Specifically, the coarse inorganic particles may include inorganic materials that may act as crystallizing agents, reactants, or both, and may react with each other and / or with the glass of the hollow glass body, thereby forming new crystalline phases at a temperature below the softening temperature of the hollow glass body. These new crystalline phases may include nano-sized grains having an increased surface area compared to the starting coarse inorganic particles and / or the hollow glass body. The nano-sized grains comprising these new secondary crystalline phases may have a surface area greater than or equal to 10 μm / g. 2 / g or even greater than or equal to 20m 2 / g of average surface area. In addition, the formation of these new crystalline phases at lower temperatures can inhibit shrinkage during the crystallization stage of firing. Specifically, the new crystalline phases of nano-sized grains can maintain their shape at temperatures greater than the softening temperature of the hollow glass body, and once formed, can act as a rigid body that can hinder or prevent the flow of the remaining amorphous glass when heated to a temperature greater than the softening temperature of the glass. Hindering glass flow can reduce the firing shrinkage of the green body structure made from the composition of this article.

[0112] The coarse inorganic particles may include: alkali metal salts, alkali metal oxides, alkali metal hydroxides, alkaline earth metal salts, alkaline earth metal oxides, alkaline earth metal hydroxides, or any combination thereof. In an embodiment, the coarse inorganic particles may include one or more of the following: MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li2BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or any combination thereof. In an embodiment, the coarse inorganic particles may be selected from the group consisting of MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li2BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or any combination thereof. In an embodiment, the coarse inorganic particles may include MgO.

[0113] The coarse inorganic particles may have a particle size of less than or equal to about 10 μm. 2 / g, less than or equal to 8m 2 / g or even less than or equal to 5m 2 / g surface area. The coarse inorganic particles may include more than 0 (zero) m 2 / g to 10m 2 / g surface area, for example: greater than 0m 2 / g to 8m 2 / g, greater than 0m 2 / g to 5m 2 / g,0.1m 2 / g to 10m 2 / g,0.1m 2 / g to 8m 2 / g, or 0.1m 2 / g to 5m 2 The coarse inorganic particles may have a median particle size (D50) of about 100 nanometers (nm) to about 100 micrometers (μm), for example, about 100 nm to about 50 μm, about 100 nm to about 1 μm, about 500 nm to about 100 μm, about 500 nm to about 50 μm, about 500 nm to about 1 μm, or about 1 μm to about 100 μm.

[0114] In an embodiment, the secondary phase precursor in the batch composition may include a combination of nano-sized inorganic particles and coarse inorganic particles. When the secondary phase precursor includes both nano-sized inorganic particles and coarse inorganic particles, the secondary phase produced after firing may include a combination of nano-sized inorganic particles and nano-sized grains (which originate from the reaction between the coarse inorganic particles and the silica-containing glass of the hollow glass body). In an embodiment, the secondary phase precursor in the batch composition may include: one or more types of nano-sized inorganic particles selected from the group consisting of gamma alumina, zirconium oxide, zeolite, magnesium oxide, silica, CeO2, TiO2, and any combination thereof; and one or more types of coarse inorganic particles selected from the group consisting of MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li2BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, and any combination thereof. In an embodiment, the secondary phase precursor may include a combination of gamma alumina and MgO.

[0115] The batch compositions disclosed herein may include a total amount of the secondary phase precursor sufficient to produce a phase having a thickness greater than or equal to 5 m 2 / g, greater than or equal to 10m 2 / g or even greater than or equal to 20m 2 / g of surface area of ​​the porous structure. In an embodiment, the batch composition may include 5 volume % to 50 volume % of the secondary phase precursor, wherein the volume percentage is based on the total bulk volume of the inorganic solid components of the composition (i.e., the hollow glass body and the secondary phase precursor). When the concentration of the secondary phase precursor in the batch composition is too low (e.g., less than about 5 volume %), the porous structure may not have sufficient surface area. When the concentration of the secondary phase precursor is too high, the porous structure may have reduced porosity, for example, a porosity of less than 50%. In embodiments, the batch composition may include the following secondary phase precursors: 5% to 45% by volume, 5% to 40% by volume, 5% to 35% by volume, 5% to 30% by volume, 5% to 25% by volume, 5% to 20% by volume, 10% to 50% by volume, 10% to 45% by volume, 10% to 40% by volume, 10% to 35% by volume, 10% to 30% by volume, 10% to 25% by volume, 10% to 20% by volume, 15% to 5 0 volume %, 15 volume % to 45 volume %, 15 volume % to 40 volume %, 15 volume % to 35 volume %, 15 volume % to 30 volume %, 15 volume % to 25 volume %, 15 volume % to 20 volume %, 20 volume % to 50 volume %, 20 volume % to 45 volume %, 20 volume % to 40 volume %, 20 volume % to 35 volume %, 20 volume % to 30 volume %, or 20 volume % to 25 volume %, wherein the volume percentages are based on the total bulk volume of the inorganic solid components of the composition. In an embodiment, the batch composition may include about 15 volume % to about 35 volume % of the secondary phase precursor, based on the total bulk volume of the inorganic solid components of the composition. In an embodiment, the batch composition may include about 20 volume % of the secondary phase precursor, based on the total bulk volume of the inorganic solid components of the composition.

[0116] The batch composition may include from about 5% to about 95% by weight of the secondary phase precursor, wherein the weight percentages are based on the total weight of the hollow glass body and the secondary phase precursor. The batch composition may include: from about 5% to about 90% by weight, from about 5% to about 80% by weight, from about 5% to about 70% by weight, from about 25% to about 95% by weight, from about 25% to about 90% by weight, from about 25% to about 80% by weight, from about 25% to about 70% by weight, from about 50% to about 90% by weight, from about 50% to about 80% by weight, or from about 50% to about 70% by weight of the secondary phase precursor, based on the total weight of the hollow glass body and the secondary phase precursor. In embodiments, the batch composition may include 5% to 95% by weight of the secondary phase precursor, based on the total weight of the batch composition (e.g., including the liquid vehicle and the organic system in addition to the hollow glass body and the secondary phase precursor), such as: 5% to 90%, 5% to 80%, 5% to 50%, 5% to 40%, 5% to 35%, 10% to 95%, 10% to 90%, 10% to 80%, 10% to 50%, 10% to 40%, 10% to 35%, 20% to 95%, 20% to 90%, 20% to 80%, 20% to 50%, 20% to 40%, or 20% to 35% by weight of the secondary phase precursor, based on the total weight of the batch composition.

[0117] In embodiments, the secondary phase precursor may include both nano-sized inorganic particles and coarse inorganic particles. In these embodiments, the batch composition may include from about 5% to about 25% by volume of the nano-sized inorganic particles and from about 5% to about 25% by volume of the coarse inorganic particles, based on the total bulk volume of the inorganic solid components of the composition.

[0118] The secondary phase precursor may be provided as a dry powder or as a dispersion or suspension of the secondary phase precursor in a liquid solvent. In embodiments, the secondary phase precursor may be provided as a dispersion or suspension of the secondary phase precursor in a solvent and may also include an optional dispersant. The weight % and volume % discussed herein are based on the weight of the secondary phase precursor itself, without taking into account the solvent and / or dispersant.

[0119] The batch composition may also include an organic system. The organic system may include one or more binders, additives, or combinations thereof. In an embodiment, the batch composition disclosed herein may include one or more binders. The binder is used to bind the particles together to form a green structure that can maintain a honeycomb shape or other shapes until the green structure can be fired. The binder can be any type of cellulose or cellulose derivative. The binder can also be a polymer binder, such as but not limited to: polyvinyl alcohol (PVA) polymer, polyvinyl pyrrolidone (PVP) polymer, or other polymers or combinations of polymers. In an embodiment, the batch composition may include a binder, which includes: cellulose, cellulose derivatives, polymer binders, or combinations thereof. In an embodiment, the binder may include methyl cellulose, carboxymethyl cellulose (CMC), or a combination thereof. In an embodiment, the batch composition may include one or more binders selected from the group consisting of methyl cellulose, CMC, PVA, PVP, and combinations thereof. In embodiments, the composition may include 5 wt % to 20 wt % binder, based on the total weight of the hollow glass body and secondary phase precursor in the batch composition (ie, (weight of binder) / ((weight of hollow glass body)+(weight of secondary phase precursor))).

[0120] In an embodiment, the batch composition may include one or more additives, such as: slip agents and / or lubricants, such as oils or sodium stearate, but not limited thereto. In an embodiment, the additive may act as a rheology modifier to make a batch composition that is easier to extrude, to increase the extrusion rate, and to improve the quality of the porous structure (specifically, the porous structure of the honeycomb shape). In an embodiment, the additive may include a sintering aid, such as but not limited to sodium stearate or other sintering aids. In an embodiment, the additive may include a pore former, such as an organic pore former, such as starch (e.g., corn starch, pea starch, etc.). The additive may be sodium stearate, oils, graphite, starch, other additives, or a combination of these. In an embodiment, the batch composition may include one or more additives selected from the group consisting of sodium stearate, oils, graphite, starch, and a combination of these. The batch composition may include greater than 0% to 5% by weight of additives (e.g., 0.1% to 5% by weight of additives), based on the total weight of the hollow glass body and the secondary phase precursor. In an embodiment, the batch composition may not include additives. In an embodiment, the composition may not include sodium stearate or other sintering aids. In an embodiment, the composition may not include a pore former, such as starch.

[0121] The batch composition may include a liquid vehicle. The liquid vehicle may be water, one or more alcohols, or any combination thereof. In an embodiment, the liquid vehicle is water. The amount of the liquid vehicle in the batch composition may be sufficient to enable the batch composition to be extruded or otherwise shaped or formed into a green structure, but not so much that the green structure cannot maintain its shape after formation. The batch composition may contain about 25% to about 100% by weight or about 30% to about 70% by weight of the liquid vehicle, based on the total weight of the hollow glass body and the secondary phase precursor.

[0122] In embodiments, the batch composition may have a batch density (eg, a "wet batch" density) of less than or equal to 1.5 g / cm 3 , for example: less than or equal to 1.0g / cm 3 , less than or equal to 0.5g / cm 3 , or even less than or equal to 0.3 g / cm 3 The batch density of the batch composition may be greater than or equal to 0.1 g / cm 3 In embodiments, the green structure comprising the batch composition and the batch materials may float in water (ie, have a specific gravity less than 1 compared to water), while the finished porous structure (after firing and / or fracturing of the hollow glass body) may sink in water.

[0123] The peak firing temperature of the batch composition of the present disclosure comprising a hollow glass body and a secondary phase precursor can be less than the peak firing temperature of the batch composition having only a hollow glass body. The batch composition of the present disclosure can have a peak firing temperature of less than or equal to about 1000°C, less than or equal to about 950°C, less than or equal to about 900°C, or even less than or equal to about 850°C. The batch compositions disclosed herein may have a peak firing temperature of about 500°C to about 1000°C, about 500°C to about 950°C, about 500°C to about 900°C, about 500°C to about 850°C, about 500°C to about 800°C, about 600°C to about 1000°C, about 600°C to about 950°C, about 600°C to about 900°C, about 600°C to about 850°C, about 600°C to about 800°C, about 800°C to about 1000°C, about 800°C to about 970°C, about 800°C to about 950°C, about 800°C to about 900°C, about 850°C to about 1000°C, about 850°C to about 970°C, about 850°C to about 950°C, or about 900°C to about 1000°C.

[0124] The porous structure disclosed herein can be prepared from a batch composition according to a method comprising: preparing a batch composition, forming a green structure from the composition, and firing the green structure at a temperature of less than or equal to 1000° C. Firing the green structure bonds the hollow glass body to the secondary phase precursor and breaks at least a portion of the hollow glass body to form a porous structure. When the secondary phase precursor includes coarse inorganic particles, firing can also result in a reaction between the glass of the hollow glass body and the coarse inorganic particles to produce a porous structure having a high surface area (e.g., >10 m 2 The resulting porous structure may have a porosity greater than or equal to 50% and a pore size greater than or equal to 5 m 2 / g average surface area.

[0125] The preparation of the batch composition may include combining the hollow glass body, the secondary phase precursor, the liquid vehicle, and the organic system (e.g., a binder and / or an additive). The batch composition may be any constituent component and may have any of the properties described above for the batch composition. The constituent components of the batch composition may be combined and mixed according to known methods. The hollow glass body, the secondary phase precursor, the liquid vehicle, the binder, and the additive may have any of the characteristics, properties, or amounts described above. The average pore size, porosity, surface area, or a combination of these properties of the porous structure may be modified by changing the constituent components and / or the relative concentrations of the constituent components of the batch composition. Specifically, the methods disclosed herein may include adjusting the average pore size, porosity, and / or surface area of ​​the porous structure by changing the type of secondary phase precursor and / or the ratio of the secondary phase precursor relative to the hollow glass body in the batch composition. The average pore size may also be adjusted by changing the peak firing temperature, the hold / residence time at the peak firing temperature, the temperature ramp rate during the heating process, or a combination of these. Increasing the peak firing temperature, increasing the hold / dwell time at the peak firing temperature, and increasing the temperature ramp rate during heating can all increase the average pore size to the point where the monolithic structure is not completely melted. In embodiments, the method may include modifying the porosity and / or surface area of ​​the porous structure by varying the type of secondary phase precursor and / or the relative amount of secondary phase precursor in the batch composition.

[0126] After preparing the batch composition, the methods disclosed herein may include forming a green structure from the batch composition. In embodiments, the batch composition may be formed into a green structure having a honeycomb shape having a plurality of elongated channels extending through the green structure (e.g., Figure 1 The green structure may be formed by extrusion, molding, casting, rolling, calendaring, 3D printing, or other forming processes, or a combination of these. Extruding the green structure may be useful for forming a porous structure (e.g., Figure 1A through-channel is formed in a porous structure of a honeycomb shape (for example, Figure 1 The elongated channels 212 shown) or other regular features in the corresponding green structure are particularly effective. However, in other contemplated embodiments, such green structures can be molded, cast, or otherwise formed or processed, which can better or alternatively preserve the integrity of the hollow glass body. In other contemplated embodiments, the hollow glass body can be extruded or otherwise formed into a shape that is significantly different from the shape of the hollow glass body. Figure 1 and 2 Those of the porous structures 112, 212 shown.

[0127] In an embodiment, the batch composition can be extruded to form a green body structure. A twin-screw extruder or other suitable extrusion machine can be used to complete the extrusion. The extrusion rate and pressure of the batch composition comprising the hollow glass body and the secondary phase precursor can retain most (e.g., more than 50%, more than 75%, more than 90%) of the integrity of the hollow glass body. In this regard, in other embodiments considered, the extrusion rate and pressure can retain the integrity of many (but not most, for example: less than 50%, but at least 25% or at least 20%) of the hollow glass body. Retaining the integrity of the hollow glass body can achieve that the hollow glass body occupies more space volume in the green body structure, with cavities (i.e., the internal volume of the hollow glass body) between the hollow glass bodies and in the hollow glass body. The extrusion rate and pressure can vary depending on the size of the hollow glass body, the glass of the hollow glass body, and the extrusion device. In some embodiments, the extrusion pressure range can be less than 2500psi, for example: less than 2000psi and / or at least 500psi.

[0128] After forming the green structure from the batch composition, the method may include firing the green body to a peak firing temperature. The conditions and operation of the green structure during heating are such that adjacent hollow glass bodies can physically interact with each other, such as directly bond to each other (e.g., sintering, welding, melting into each other), but do not completely lose their respective structures. In other words, the conditions and operation during firing are such that the hollow glass bodies do not completely liquefy and do not completely lose structure, but instead become bonded to each other so that the resulting porous structure in the aggregate is cohesive and rigid.

[0129] In addition, in embodiments, the conditions and operation of the green structure during heating can cause many of the hollow glass bodies (e.g., a majority, >90%, >95%, >99%) to breach or break, such as due to internal gas expansion and / or due to devitrification or other means. The green structure can be heated to a point where the hollow glass bodies lose integrity and the glass of the hollow glass bodies shatters or breaks in any other way, but the hollow glass bodies do not completely liquefy or completely lose structure. In other contemplated embodiments, the hollow glass bodies can be breached by microwaves, acoustic energy, or other phenomena. As disclosed herein, causing the hollow glass bodies contained in the green structure to breach can achieve the maintenance of the cavities of the hollow glass bodies and / or even enlargement and mutual bonding to create a porous network in the porous structure.

[0130] In an embodiment, the secondary phase precursor may include nano-sized inorganic particles, and firing the green structure may bond the hollow glass body and the nano-sized inorganic particles together and may fracture at least a portion of the hollow glass body to form a porous structure having a porosity greater than or equal to 50% and a void volume greater than or equal to 5 μm. 2 In addition or alternatively, in an embodiment, the secondary phase precursor may include coarse inorganic particles (which include oxides, hydroxides, salts or combinations thereof of alkali metals and / or alkaline earth metals); and the green structure is fired to cause a reaction between the silica-containing glass of the hollow glass body and the coarse inorganic particles, thereby producing nano-sized grains having a larger surface area than the coarse inorganic particles, and at least a portion of the hollow glass body may be broken to form a porous structure with a porosity greater than or equal to 50% and a surface area greater than or equal to 5 m 2 / g porous structure.

[0131] In an embodiment, during the firing process, the green structure may be heated, for example, by firing the green structure in a furnace, laser heating the green structure, or other heating methods. The heating may burn off the binder, char the binder, chemically transform the binder, or affect the binder in any other way. In an embodiment, the method may include heating the green structure to at least the softening temperature of the glass of the hollow glass body. However, the hollow glass body is not overheated (e.g., heated to a temperature far above the liquidus temperature of the glass), at which the hollow glass body may completely lose cohesion or structure. The method may include heating the green structure to a peak firing temperature that is at least greater than or equal to the softening temperature of the glass and less than about 1000°C. When the peak firing temperature is greater than or equal to about 1000°C, it is found that the surface area of ​​the completed porous structure drops sharply. Thus, at a peak firing temperature greater than or equal to about 1000°C, it is difficult to obtain a surface area greater than about 5m 2 / g porous structure. At temperatures below the softening temperature of the glass, fewer hollow glass bodies are broken apart during firing, resulting in low porosity. The softening temperature may depend on the glass composition of the hollow glass body.

[0132] Depending on the glass composition used to make the green structure and the materials in the composition, firing the green structure can include heating the green structure to a peak firing temperature of greater than or equal to about 500°C, greater than or equal to about 600°C, greater than or equal to about 700°C, greater than or equal to about 750°C, greater than or equal to about 800°C, or even greater than or equal to about 850°C, and less than or equal to about 1000°C, less than or equal to about 975°C, less than or equal to about 950°C, less than or equal to about 925°C, or even less than or equal to 900°C. In embodiments, the method may include heating or firing the green structure to a peak firing temperature of less than or equal to about 1000°C, for example: 500°C to 1000°C, 500°C to 975°C, 500°C to 950°C, 500°C to 925°C, 500°C to 900°C, 600°C to 1000°C, 600°C to 975°C, 600°C to 950°C, 600°C to 925°C, 600°C to 900°C, 700°C to 1000°C, 700°C to 975°C, 700°C to 950°C, 700°C to 925°C, 700°C to 900°C, 750°C to 1000°C, 750°C to 975°C. ℃, 750℃ to 950℃, 750℃ to 925℃, 750℃ to 900℃, 800℃ to 1000℃, 800℃ to 975℃, 800℃ to 950℃, 800℃ to 925℃, 800℃ to 900℃, 825℃ to 1000℃, 825℃ to 975℃, 825℃ to 950℃, 825℃ to 925℃, 825℃ to 900℃, 850℃ to 1000℃, 850℃ to 975℃, 850℃ to 950℃, 850℃ to 925℃, 850℃ to 900℃, 900℃ to 1000℃, or any range or sub-range between each of these temperatures.

[0133] In an embodiment, firing of the green structure may include performing a firing process such that the green structure is systematically heated to a peak firing temperature. In an embodiment, the firing process may include: heating the green structure to the peak firing temperature at a substantially constant temperature ramp rate of about 50°C per hour to about 300°C per hour; maintaining the green structure at the peak firing temperature for a period of 1 hour to 10 hours; and then cooling the green structure back to ambient temperature. In an embodiment, firing the green structure may include ramping the green structure to a peak firing temperature less than or equal to about 1000°C (e.g., about 500°C to about 1000°C), and maintaining the green structure at the peak firing temperature for a period of 1 hour to 10 hours.

[0134] In an embodiment, firing the green structure may include debinding the batch composition of the green structure. The debinding of the green structure may include heating the green structure from ambient temperature to a first temperature (e.g., a fixed temperature and / or multiple temperatures within a limited range) at a substantially constant ramp rate of 50°C per hour to about 300°C per hour. The first temperature may be within the debinding temperature range of the batch composition. The debinding temperature range may be 200°C to 400°C or 300°C to 400°C. The first temperature is less than the lower crystallization temperature of the glass of the hollow glass body, which is the temperature at which crystallization of the glass begins to occur. The green body may be maintained at the first temperature for a first residence time, which may be at least 1 minute, such as 1 minute to 10 hours or 1 hour to 10 hours. Alternatively or additionally, in an embodiment, at the first temperature, the temperature ramp rate may be reduced to a temperature ramp rate of less than 50°C per hour, less than or equal to 20°C per hour, less than 10°C per hour, or even less than 5°C per hour. The temperature ramp rate may be maintained at a lower temperature ramp rate until a debinding temperature of about 400° C. is reached, at which point the temperature ramp rate may be returned to the first ramp rate of 50° C. per hour to 300° C. per hour. In an embodiment, the firing process of firing the green structure to produce the porous structure may not include debinding of the composition of the green structure.

[0135] In an embodiment, the temperature may be increased to a second temperature. The second temperature may be within the crystallization range of the glass, such as a temperature greater than the lower crystallization temperature of the glass of the hollow glass body and less than the upper crystallization temperature. The second temperature may be greater than 400°C, such as 500°C to 800°C. The green structure may be maintained at the second temperature for a second residence time of at least 1 minute, such as 1 hour to 10 hours. In an embodiment, during the firing process, the temperature is increased from the second temperature to a third temperature having a third residence time, such as wherein the second temperature is greater than 400°C and less than the softening point of the glass of the hollow glass body, and the third temperature is greater than the softening point of the glass of the hollow glass body. The third temperature may be a peak firing temperature. The third residence time may be at least 1 minute, such as 1 hour to 10 hours.

[0136] In an embodiment, firing the green structure may include heating the green structure to a debonding temperature of 200°C to 400°C, and maintaining the green structure at the debonding temperature for a debonding residence time. The debonding residence time may be 1 hour to 10 hours. In an embodiment, the firing of the green structure may not include a debonding residence time, and the temperature of the green structure may be continuously raised through the debonding temperature range. The firing of the green structure may also include raising the temperature of the green structure to a lower crystallization temperature of the hollow glass body at a first heating rate of greater than 100°C per hour to 250°C per hour. At the lower crystallization temperature of the hollow glass body, firing may include: slowing the temperature rise rate to a second heating rate of less than 100°C per hour, or maintaining the temperature of the green structure at a temperature between the lower crystallization temperature of the glass and the upper crystallization temperature of the glass for a period of 1 hour to 10 hours. Slowing the temperature rise rate within the crystallization temperature range or maintaining the green structure at a temperature within the crystallization temperature range can reduce the shrinkage of the porous structure relative to the green structure, as will be further described herein. Firing of the green structure can also include raising the temperature of the green structure to a peak firing temperature of the green structure and maintaining the green structure at the peak firing temperature for a period of time from 1 hour to 10 hours. The firing process transforms the green structure into a porous structure, as described herein.

[0137] After firing the green structure to the peak firing temperature and maintaining the green structure at the peak firing temperature for a period of time to produce the porous structure, the porous structure can be cooled back to ambient temperature. The method disclosed herein for making a porous structure can include cooling the porous structure back to ambient temperature after firing at the peak firing temperature. In an embodiment, the method can include cooling the porous structure back to a temperature that is at least 100°C lower than the heating temperature of the green structure during firing (i.e., the peak firing temperature). In an embodiment, the method can include cooling the porous structure to a temperature less than 100°C or even less than 50°C, such as a temperature of 20°C to 100°C or 20°C to 50°C. During the cooling process, adjacent hollow glass bodies (which may not be so spherical at this time) are and / or remain physically bonded to each other, such as directly or indirectly bonded. Indirect bonding can mean that adjacent hollow glass bodies are bonded to each other through an intermediate bonding agent (e.g., nanosized inorganic particles, nanosized grains generated from coarse inorganic particles, unreacted coarse inorganic particles, residues of a binder added to the composition), or a combination of these.

[0138] In embodiments, cooling of the porous structure may include allowing the porous structure to dwell at a temperature greater than ambient temperature but less than the firing temperature. In embodiments, cooling of the porous structure may include allowing the porous structure to dwell at an annealing temperature of the glass of the hollow glass body. In some embodiments, dwelling may be in incremental steps, or in other embodiments, may be in the form of a very gradual temperature drop within a certain temperature range, both of which may allow for the formation of crystals in the material of the hollow glass body and / or may promote relaxation of residual stresses by annealing.

[0139] In embodiments, the methods disclosed herein may further include changing the average surface area of ​​the porous structure. Changing the average surface area of ​​the porous structure may include: changing the concentration of the secondary phase precursor in the batch composition, changing the type of secondary phase precursor in the batch composition, changing the firing temperature of the green structure, or a combination of these.

[0140] The porous structure produced from the batch composition, the green body structure and the firing process may include a hollow glass body and a secondary phase sintered together. The porous structure produced from the batch composition may mainly contain the constituent components of the glass and the secondary phase from the hollow glass body. The porous structure may also contain a small amount of binder or a compound produced by the firing of the binder and other additives. At least a portion of the hollow glass bodies in the porous structure are broken. In an embodiment, the porous structure may have greater than or equal to 50%, greater than or equal to 70%, greater than or equal to 80%, or even greater than or equal to 90% and less than or equal to 100% of the hollow glass bodies are broken. The cavities defined in the individual broken hollow glass bodies may be open to each other to form a cavity that extends through the porous structure and reaches its outer surface.

[0141] After the green structure is fired, the porous structure may include: 5% to 95% by weight of glass, crystallized glass, or both; and 5% to 95% by weight of a secondary phase, based on the total weight of the porous structure. Glass, crystallized glass, or both may include constituent components of the silica-containing glass composition of the hollow glass body. In an embodiment, the porous structure may include a significant proportion of glass, crystallized glass, or both, for example, at least 5%, at least 25% by weight, at least 40%, at least 45%, at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, or even at least 95%, by weight of glass, crystallized glass, or both, based on the total weight of the porous structure. For those in the industry, it may be surprising or counterintuitive that such a large proportion of the porous structure 112 is formed of glass and / or crystallized glass, because they may expect such structures to be particularly fragile and / or not held together at all. In an embodiment, the porous structure may contain: greater than or equal to 5 wt %, greater than or equal to 25 wt %, greater than or equal to 40 wt %, greater than or equal to 50 wt %, or even greater than or equal to 60 wt % of silica glass, crystallized silica glass, or both, based on the total weight of the porous structure. The porous structure may contain: less than or equal to 95 wt %, less than or equal to 90 wt %, less than or equal to 80 wt %, less than or equal to 70 wt %, or even less than or equal to 60 wt % of silica glass, crystallized silica glass, or both, based on the total weight of the porous structure. The porous structure can contain: 5 wt % to 95 wt %, 25 wt % to 90 wt %, 25 wt % to 80 wt %, 25 wt % to 70 wt %, 25 wt % to 60 wt %, 25 wt % to 50 wt %, 25 wt % to 40 wt %, 40 wt % to 90 wt %, 40 wt % to 80 wt %, 40 wt % to 70 wt %, 40 wt % to 60 wt %, 50 wt % to 90 wt %, 50 wt % to 80 wt %, 50 wt % to 70 wt %, 60 wt % to 90 wt %, 60 wt % to 80 wt %, or 60 wt % to 70 wt % silica glass, crystallized silica glass, or both, based on the total weight of the porous structure.

[0142] At least some of the glass of the hollow glass body may be devitrified to form a crystallized silica glass having one or more crystalline phases. The crystalline phase of the crystallized silica glass may include constituent components from a secondary phase precursor, particularly when the secondary phase precursor comprises coarse inorganic particles. The gradual heating as disclosed herein and the retention of the green structure at the peak firing temperature may promote crystal growth in the silica glass of the hollow glass body. Crystallized silica glass may increase the strength of the porous structure compared to non-crystalline amorphous glass. Although the batch composition of the green structure may include an amorphous hollow glass body, the porous structure after firing may be a glass ceramic having a crystallinity greater than or equal to 45% by weight (wt%), for example: greater than or equal to 50 wt%, greater than or equal to 60 wt%, greater than or equal to 70 wt%, greater than or equal to 80 wt%, greater than or equal to 90 wt%, or even greater than or equal to 95 wt%, based on the total weight of the porous structure. Based on X-ray diffraction (XRD), Rietveld analysis was used to determine the weight percentage of the crystalline phase and the residual glass phase. A D8 ENDEAVOR from Bruker equipped with Cu radiation was used. TM XRD spectra were obtained using Bruker's TOPAS TM Version 6 analysis software performs Rietveld analysis based on XRD spectra. In an embodiment, the porous structure may include an amorphous glass phase. In an embodiment, the porous structure may include less than 55 wt%, less than 50 wt%, or even less than 36 wt% amorphous phase glass, based on the total weight of glass in the porous structure. In an embodiment, the porous structure may include: 1 wt% to 55 wt%, 5 wt% to 50 wt%, 5 wt% to 36 wt%, 10 wt% to 55 wt%, 10 wt% to 50 wt%, or 10 wt% to 36 wt% amorphous phase glass, based on the total weight of the porous structure.

[0143] In embodiments, the porous structure may include from about 5 wt % to about 95 wt % of the secondary phase, based on the total weight of the porous structure, for example: from about 5 wt % to about 75 wt %, from about 5 wt % to about 60 wt %, from about 5 wt % to about 55 wt %, from about 5 wt % to about 50 wt %, from about 5 wt % to about 45 wt %, from about 5 wt % to about 40 wt %, from about 5 wt % to about 35 wt %, from about 5 wt % to about 30 wt %, from about 5 wt % to about 25 wt %, from about 5 wt % to about 20 wt %, from about 10 wt % to about 95 wt %, from about 10 wt % to about 75 wt %, from about 10 wt % to about 60 wt %, from about 10 wt % to about 55 wt %, from about 10 wt % to about 50 wt %, from about 10 wt % to about 45 wt %, from about 10 wt % to about 40 wt %, from about 10 wt % to about 35 wt %, from about 10 wt % to about 30 wt %, from about 10 wt % to about 25 wt %, from about 10 wt % to about % to about 95 wt %, about 15 wt % to about 75 wt %, about 15 wt % to about 60 wt %, about 15 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 15 wt % to about 25 wt %, about 15 wt % to about 20 wt %, about 20 wt % to about 95 wt %, about 20 wt % to about 75 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 20 wt % to about 25 wt %, or any subrange therebetween, based on the total weight of the porous structure.

[0144] As discussed above, the secondary phase may include nano-sized inorganic particles, nano-sized grains formed by the reaction of coarse inorganic particles with silica glass, or a combination of both. In embodiments, the secondary phase may include a surface area greater than or equal to 10 m 2 / g of nano-sized inorganic particles. During the firing process, the nano-sized inorganic particles can remain substantially unchanged and can provide a high surface area structure embedded in the surface of the glass from the hollow glass body. In an embodiment, the porous structure may include nanosized inorganic particles as follows: from about 5 wt % to about 95 wt %, from about 5 wt % to about 75 wt %, from about 5 wt % to about 60 wt %, from about 5 wt % to about 55 wt %, from about 5 wt % to about 50 wt %, from about 5 wt % to about 45 wt %, from about 5 wt % to about 40 wt %, from about 5 wt % to about 35 wt %, from about 5 wt % to about 30 wt %, from about 5 wt % to about 25 wt %, from about 5 wt % to about 20 wt %, from about 10 wt % to about 95 wt %, from about 10 wt % to about 75 wt %, from about 10 wt % to about 60 wt %, from about 10 wt % to about 55 wt %, from about 10 wt % to about 50 wt %, from about 10 wt % to about 45 wt %, from about 10 wt % to about 40 wt %, from about 10 wt % to about 35 wt %, from about 10 wt % to about 30 wt %, from about 10 wt % to about 25 wt %, from about 10 wt % to about 20 % to about 95 wt %, about 15 wt % to about 75 wt %, about 15 wt % to about 60 wt %, about 15 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 15 wt % to about 25 wt %, about 15 wt % to about 20 wt %, about 20 wt % to about 95 wt %, about 20 wt % to about 75 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 20 wt % to about 25 wt %, or any subrange therebetween, based on the total weight of the porous structure.

[0145] In an embodiment, the secondary phase precursor may be a coarse inorganic particle, and the secondary phase may include nano-sized grains, which are the reaction product of the reaction between the silica-containing glass of the hollow glass body and the coarse inorganic particles. The reaction between the silica-containing glass and the coarse inorganic particles may produce nano-sized grains containing one or more secondary crystalline phases. The secondary crystalline phases of the nano-sized grains may include, but are not limited to: forsterite, clinopyroxene, diopside, wollastonite, pseudowollastonite, orthorhombic calcium calcite, cristobalite, romagnesian stone, corundum, zirconia, other secondary crystalline phases, or combinations thereof. In an embodiment, the nano-sized grains may include at least one magnesium-based crystalline phase selected from forsterite, clinopyroxene, diopside, or a combination thereof. In an embodiment, the nano-sized grains may include at least one calcium-based crystalline phase selected from wollastonite, pseudowollastonite, orthorhombic calcium calcite, cristobalite, or a combination thereof. In an embodiment, the nano-sized grains may include one or more crystalline phases selected from romagnesian stone, corundum, zirconia, or a combination thereof.

[0146] In embodiments, the porous structure may include nano-sized grains as follows: about 5 wt % to about 95 wt %, about 5 wt % to about 75 wt %, about 5 wt % to about 60 wt %, about 5 wt % to about 55 wt %, about 5 wt % to about 50 wt %, about 5 wt % to about 45 wt %, about 5 wt % to about 40 wt %, about 5 wt % to about 35 wt %, about 5 wt % to about 30 wt %, about 5 wt % to about 25 wt %, about 5 wt % to about 20 wt %, about 10 wt % to about 95 wt %, about 10 wt % to about 75 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 55 wt %, about 10 wt % to about 50 wt %, about 10 wt % to about 45 wt %, about 10 wt % to about 40 wt %, about 10 wt % to about 35 wt %, about 10 wt % to about 30 wt %, about 10 wt % to about 25 wt %, about 10 wt % to about 20 wt %. % to about 95 wt %, about 15 wt % to about 75 wt %, about 15 wt % to about 60 wt %, about 15 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 15 wt % to about 25 wt %, about 15 wt % to about 20 wt %, about 20 wt % to about 95 wt %, about 20 wt % to about 75 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 20 wt % to about 25 wt %,

[0147] In an embodiment, the secondary phase may also include nano-sized inorganic particles (having a diameter greater than or equal to 10 m). 2 / g of surface area) and nano-sized crystallites (which include the reaction product of the reaction between the silica-containing glass and the coarse inorganic particles).

[0148] The porous structure may have a high porosity of greater than or equal to about 50%, as determined by mercury intrusion porosimetry as described herein. In embodiments, the porous structure may have a porosity of greater than or equal to about 55%, greater than or equal to about 60%, or even greater than or equal to about 65%, as determined by mercury intrusion porosimetry. In embodiments, the porous structure may have a porosity of about 50% to about 80%, about 50% to about 75%, about 50% to about 70%, about 50% to about 65%, about 55% to about 80%, about 55% to about 75%, about 55% to about 70%, about 55% to about 65%, about 60% to about 80%, about 60% to about 75%, about 60% to about 70%, about 60% to about 65%, or about 65% to about 80%. The porosity may be modified by varying the amount of secondary phase precursor in the batch composition. In embodiments, the batch composition for making the porous structure may have less than or equal to 50 volume %, less than or equal to 25 volume %, or even less than or equal to 12 volume % of the secondary phase precursor, based on the total bulk volume of the inorganic solid components of the composition (i.e., the hollow glass body and the secondary phase precursor), thereby providing a porosity greater than 50% (e.g., 50% to 80%).

[0149] The porous structure has a plurality of Figure 2 The outer surface having an opening on the outer surface 214 may have at least about 1 cubic centimeter (cm 3 ), for example at least about 2 cm 3 , for example at least about 10 cm 3 , for example at least about 50 cm 3 , and / or not more than about 2000cm 3 , for example not more than about 1000cm 3 In embodiments, such as for large frontal area filters, the total volume may be much greater than 2000 cm 3 .

[0150] As discussed above, the porous structures disclosed herein may have a thickness greater than or equal to about 5 m 2 In an embodiment, the porous structure may have a specific surface area greater than or equal to about 10 m 2 / g or even greater than or equal to about 20m 2The specific surface area of ​​the porous structure can be determined by Brunauer-Emmett-Teller (BET) surface area analysis using N2 adsorption. To determine the specific surface area, a sample of the porous structure was prepared by heating at 300°C and evacuating under vacuum for 4 hours to remove any impurities. The prepared sample was then cooled with liquid nitrogen and analyzed by using TRISTAR TM II 3020 surface area and porosity analyzer to measure the volume of gas adsorbed at a specific pressure. The specific surface area of ​​the porous structure is then determined by analyzing the N2 adsorption isotherm generated by the specific surface area and porosity analyzer using the BET method. In an embodiment, the porous structure may have a specific surface area of ​​about 5 m 2 / g to about 350m 2 / g, about 5m 2 / g to about 250m 2 / g, about 5m 2 / g to about 200m 2 / g, about 5m 2 / g to about 100m 2 / g, about 5m 2 / g to about 90m 2 / g, about 5m 2 / g to about 80m 2 / g, about 5m 2 / g to about 50m 2 / g, about 10m 2 / g to about 350m 2 / g, about 10m 2 / g to about 250m 2 / g, about 10m 2 / g to about 200m 2 / g, about 10m 2 / g to about 100m 2 / g, about 10m 2 / g to about 90m 2 / g, about 10m 2 / g to about 80m 2 / g, about 10m 2 / g to about 50m 2 / g, about 20m 2 / g to about 350m 2 / g, about 20m 2 / g to about 250m 2 / g, about 20m 2 / g to about 200m 2 / g, about 20m 2 / g to about 100m2 / g, about 20m 2 / g to about 90m 2 / g, about 20m 2 / g to about 80m 2 / g, about 20m 2 / g to about 50m 2 / g, about 30m 2 / g to about 350m 2 / g, about 30m 2 / g to about 250m 2 / g, about 30m 2 / g to about 200m 2 / g, about 30m 2 / g to about 100m 2 / g, about 30m 2 / g to about 90m 2 / g, about 30m 2 / g to about 80m 2 / g, or about 30m 2 / g to about 50m 2 The average surface area of ​​the porous structure can be modified by changing the amount or type of the secondary phase precursor, increasing or decreasing the peak firing temperature during firing of the green structure, or a combination of these.

[0151] The porous structure of the present disclosure may have a median pore size of 1 μm to 50 μm, 1 μm to 20 μm, 1 μm to 16 μm, 2 μm to 50 μm, 2 μm to 20 μm, 2 μm to 16 μm, 5 μm to 50 μm, 5 μm to 20 μm, 5 μm to 16 μm, 8 μm to 50 μm, 8 μm to 20 μm, 8 μm to 16 μm, 12 μm to 50 μm, 12 μm to 20 μm, or 12 μm to 16 μm. The median pore size may refer to a d50 value corresponding to 50% of the pore size of the porous structure measured by mercury intrusion porosimetry as discussed herein. The median pore size may be adjustable by adjusting the packing pattern of the particles of the hollow glass body and the inorganic powder. Compared to porous structures made with only hollow glass bodies without inorganic powders, the combination of hollow glass bodies and inorganic powders herein can achieve a wider range of pore size distribution for porous structures. The median pore size can be adjusted within the range of 1 μm to 50 μm.

[0152] The porous structure may have a pore size distribution characterized by a D factor. The D factor of a porous structure is defined as being equal to (d 50 -d 10 ) / d 50 d 50The value d refers to the median pore diameter of the porous structure when 50% by volume of the open porosity of the porous structure is invaded by mercury during porosity measurements performed according to the methods disclosed herein. As used herein, the value d 10 10% of the pore volume is composed of pores with diameters smaller than d 10 The pore size of the porous structure is 10 The value is equal to the pore diameter when 90 volume % of the open porosity of the porous structure is invaded by mercury during the porosity measurement. In an embodiment, the porous structure including the hollow glass body and the inorganic powder may have a pore size distribution (d ) of about 0.1 to about 1.0. 50 -d 10 ) / d 50 , for example: about 0.1 to about 0.9, about 0.1 to about 0.8, about 0.2 to about 1, about 0.2 to about 0.9, about 0.2 to about 0.8, about 0.3 to about 1.0, about 0.3 to about 0.9, about 0.3 to about 0.8, about 0.4 to about 1, about 0.4 to about 0.9, about 0.4 to about 0.8, about 0.5 to about 1, about 0.5 to about 0.9, or about 0.5 to about 0.8.

[0153] The porous structure made from the batch composition comprising the hollow glass body and the secondary phase precursor may exhibit a shrinkage of less than or equal to 15%, less than or equal to 10%, less than or equal to 8%, less than or equal to 5%, less than or equal to 2, or even less than or equal to 1% compared to the green structure before firing comprising the batch composition. In embodiments, the size and shape of the porous structure may be within 15%, within 10%, within 8%, within 5%, within 2%, or even within 1% of the size and shape of the green structure before firing comprising the batch composition. Reduced shrinkage may also provide improved control over the geometry of the fired article and may reduce substrate defects due to shrinkage and other features.

[0154] In embodiments, the porous structure may have a honeycomb shape including a plurality of elongated channels extending through at least a portion of the porous structure, as described above with respect to Figure 1 The porous structure may have a pore density (i.e., the number of elongated channels per unit cross-sectional area) of greater than or equal to 50 pores per square inch (cpsi), for example, greater than or equal to 100 cpsi, greater than or equal to 200 cpsi, or greater than or equal to 300 cpsi. The porous structure may have a pore density of less than or equal to 400 cpsi.

[0155] Each elongated channel can be separated by a pore wall. As discussed above, the strength of the porous structure made from the hollow glass body and the secondary phase precursor can achieve a reduction in the mesh thickness of the porous structure (i.e., the wall thickness between the elongated channels of the honeycomb-shaped porous structure). The porous structure disclosed herein can have a mesh thickness less than or equal to 10 mils (i.e., one thousandth of an inch), for example, not more than 8 mils, for example, not more than 7 mils, for example, not more than 6 mils, for example, not more than 5 mils. The porous structure disclosed herein can have a mesh thickness of 2 mils to 10 mils, 2 mils to 8 mils, 2 mils to 7 mils, 2 mils to 6 mils, or 2 mils to 5 mils. In an embodiment, the porous structure can have a combination of a pore density and a mesh thickness of about 200 / 8 (i.e., recorded as (pore density, in cpsi) / (mesh thickness, in mils)). In other embodiments, the porous structure may have a combination of cell density and mesh thickness: 400 / 7, 400 / 6, 400 / 5, 400 / 4, 400 / 3, 400 / 2, 300 / 7, 300 / 6, 300 / 5, 300 / 4, 300 / 3, 300 / 2, 200 / 7, 200 / 6, 200 / 5, 200 / 4, 100 / 8, 100 / 7, 100 / 6, 100 / 5, 50 / 8, 50 / 7, or 50 / 6, where the cell density to the left of the " / " is in cpsi and the mesh thickness to the right of the " / " is in mils. In an embodiment, the porous structure may have a honeycomb shape having a cell density of less than 400 cells per inch and a mesh thickness between 2 mils and 8 mils.

[0156] In embodiments, the porous structure can have a cylindrical geometry and can have a diameter greater than or equal to 2 inches, greater than or equal to 4 inches, greater than or equal to 6 inches, greater than or equal to 8 inches, greater than or equal to 12 inches, or greater than or equal to 24 inches. The diameter of the porous structure can be less than or equal to 64 inches or less than or equal to 36 inches. In embodiments, the cross-section of the porous structure can have a generally square, rectangular, or other polygonal geometry with a side length greater than or equal to 2 inches, greater than or equal to 4 inches, greater than or equal to 6 inches, greater than or equal to 8 inches, greater than or equal to 12 inches, or greater than or equal to 24 inches. The side length of the porous structure can be less than or equal to 64 inches or less than or equal to 36 inches. Other embodiments contemplated have other sizes or shapes.

[0157] As discussed above, the porous structures disclosed herein can be used as substrates for CO2 capture applications. In CO2 capture applications, one or more CO2 adsorbents can be deposited onto the surface of the porous structure and / or into the cavity of the porous substrate to produce a CO2 capture device. Figure 3, schematically shows an embodiment of a CO2 capture device 300 comprising a porous structure 112 disclosed herein. In an embodiment, the CO2 capture device 300 may include a porous structure 112 having a plurality of channels 212 extending therethrough. The porous structure 112 may have any composition, property, or characteristic discussed above for the porous structure. The CO2 capture device 300 may also include at least one CO2 adsorbent 302 bonded to a surface 218 of the porous structure 112 and / or in a cavity of the porous structure 112.

[0158] The CO2 adsorbent 302 may include, but is not limited to, one or more of the following: polyethyleneimine (PEI), monoethanolamine (MEA), diethanolamine (DEA), poly(propyleneimine) (PPI), phenylpropanolamine (PPA), NaOH, Na2CO3, NaHCO3, KOH, K2CO3, KHCO3, or a combination thereof. In an embodiment, the CO2 adsorbent 302 may include PEI. The at least one CO2 adsorbent 302 may be directly bonded to a surface 218 of the porous structure 112, such as a surface defining a plurality of channels 212 extending through the porous structure 112 and / or a cavity surface of the porous structure 112. The porous structure 112 may have a thickness of greater than or equal to 5 m 2 The high surface area of ​​100 g / g can achieve direct bonding of the CO2 sorbent 302 to the surface 218 of the porous structure 112 while providing sufficient surface area of ​​the CO2 sorbent 302 to efficiently adsorb CO2. In an embodiment, the CO2 capture device 300 does not have an intermediate layer disposed between the surface 218 of the porous structure and the CO2 sorbent bonded thereto.

[0159] The CO2 sorbent 302 may be applied to and bonded to the surface 218 of the porous structure 112 by any suitable method, such as, but not limited to, wash coating, dip coating, or other known methods. Bonding the CO2 sorbent 302 to the surface 218 of the porous structure does not include applying an intermediate layer to the surface 218 of the porous structure 112 and then applying the CO2 sorbent 302 to the surface of the intermediate layer.

[0160] The CO2 capture device 300 including the porous structure 112 of the present disclosure can be incorporated into a CO2 capture process. Specifically, any porous structure disclosed herein can be incorporated into a CO2 capture process including an adsorption / desorption unit. Figure 4, schematically showing one embodiment of a system 400 for performing a CO2 capture process. The system 400 for CO2 capture may include: a gas source 402, a moisture generator 410, a mixing unit 420 downstream of the moisture generator 410, and a test chamber 430 downstream of the mixing unit 420. The gas source 402 may be a compressed dry air source. The compressed dry air may be divided into two streams. One stream may be delivered to the moisture generator 410, and the second stream may be delivered directly to the mixing unit 420. The moisture generator 410 may be operable to increase the moisture content of the compressed dry air so as to produce a compressed air stream 412 having a moisture content greater than the compressed dry air. The compressed air stream 412 and the second portion of the compressed dry air may be mixed in the mixing unit 420 to produce a mixed gas stream 422, which may be delivered to the test chamber 430. The test chamber 430 may include a container 432 and a CO2 capture device 300 disposed within the container 432. The CO2 capture device 300 may include any composition, feature, or property described above for the porous structure. The test chamber 430 may have an outlet 436 and an exhaust port 438 .

[0161] The porous structures disclosed herein can have a high surface area, for example, greater than or equal to 5 m 2 / g, greater than or equal to 10m 2 / g or even greater than or equal to 20m 2 / g, which can achieve the direct bonding of the CO2 adsorbent to the porous structure without an intermediate layer. The porosity of the porous structure disclosed herein can achieve the loading of a larger amount of CO2 active adsorbent material into the adsorption / desorption unit of the honeycomb-shaped porous structure per unit volume. Achieving a larger amount of CO2 adsorbent material loading per unit volume can achieve a greater CO2 adsorption capacity per unit volume of the adsorption / desorption unit compared to other types of porous media. The porous structure of the present disclosure can also have a lower thermal mass than the conventional cordierite structure, which can reduce the energy consumption of the CO2 capture process by reducing the energy required to heat the porous structure during the CO2 desorption process compared to the conventional cordierite structure. In addition, the porous structure disclosed herein can be relatively cheap compared to the conventional cordierite honeycomb structure based on CO2 that is commonly used in the CO2 capture process. In an embodiment, the CO2 capture process may include an adsorption / desorption unit, and the porous structure may be integrated into the adsorption / desorption unit.

[0162] The porous structure, assembly and structure shown in various exemplary embodiments are only schematic. Although only some embodiments are described in detail in the present disclosure, many improvements are feasible (for example, the size, scale, structure, shape and ratio of various elements, parameter values, installation arrangements, use of materials, colors, orientations), which do not essentially deviate from the novelty teachings and advantages of the subject matter described herein. Some elements shown as integrally formed can be composed of multiple parts or elements, and the position of the elements can be reversed or otherwise changed, and the properties or quantity of discrete elements or positions can be changed or altered. The order or sequence of any process, logical algorithm or method steps can be changed or reordered according to the embodiments replaced. Without departing from the scope of the present invention, the design, operating conditions and arrangement of various exemplary embodiments can be replaced, modified, changed and omitted.

[0163] Test Method

[0164] Modulus of rupture

[0165] The mechanical strength of the porous structure can be evaluated using a 4-point bending test performed according to ASTM C1161. When performing the mechanical strength test herein, the samples were cut into mini-bars of 0.25 inches by 0.5 inches by 3 inches. The 4-point bending test was completed using a 2-inch support span.

[0166] Porosimetry

[0167] Porosity, median pore volume, and pore size distribution herein are determined using mercury intrusion porosimetry performed according to standard test procedures known in the art.

[0168] Example

[0169] The embodiments described herein are further illustrated by the following examples. The following examples illustrate the formation of porous structures using the compositions and methods disclosed herein. The following examples are not intended to limit the scope of the present disclosure.

[0170] Material

[0171] The hollow glass bodies used in the embodiments of the present disclosure include three types of hollow glass bodies: HN70 hollow glass microspheres and H60 hollow glass microspheres purchased from China Zhongke Yali Technology Co., Ltd., and C-100-T hollow glass microspheres purchased from Zhongke Huaxing New Materials Co., Ltd. The following Table 3 provides the glass composition of the hollow glass bodies. The H60 hollow glass microspheres have a density of about 0.60 g / cm 3 The real density of HN70 hollow glass microspheres is about 0.7 g / cm 3 The true density of C-100-T hollow glass microspheres is about 0.6 g / cm3 The actual density of. Throughout the examples, the abbreviation HGMS may be used to represent hollow glass microspheres. The same methylcellulose binder and lubricant were used in all examples, and the liquid carrier in all examples was water.

[0172] Table 3: Properties of hollow glass microspheres

[0173]

[0174]

[0175] Example 1: Porous structure with nano-sized inorganic particles (ie, gamma alumina) as secondary phase precursor

[0176] In Example 1, nano-sized inorganic particles (i.e., gamma alumina) were used as secondary phase precursors to prepare a porous structure. Table 4 provides the batch composition used to make the porous structure of Example 1. The gamma alumina (γ-Al2O3) used in Example 1 has a particle size of about 230 m 2 / g of initial surface area, which can be used to increase the surface area of ​​the substrate. The hollow glass body used in Example 1 is the H60 hollow glass microsphere in Table 3. For Example 1, the hollow glass body, gamma alumina, methyl cellulose binder, lubricating oil and water are combined together to produce a batch composition, which is then extruded into a green structure having a honeycomb shape. The green structure is then fired according to the firing process disclosed herein to produce the porous structure of Example 1. For samples 1A-1E, the peak firing temperature varies from 820°C to 1120°C. Table 4 shows the results from samples 1A-1E having a high surface area (e.g., >100m 2 The porosity and surface area of ​​the porous structures of samples 1A-1E obtained by firing the nanosized inorganic particles with a surface area of ​​about 89 m / g were calculated. The best result was obtained at a firing temperature of 820°C in sample 1A, which produced a porosity of 55% and a surface area of ​​about 89 m 2 As shown in Table 4, when the peak firing temperature increases above 1000°C, the surface area decreases significantly while the total porosity remains unchanged.

[0177] Table 4

[0178]

[0179]

[0180] See now Figures 5A-5E , provides SEM images of the porous structures of Example 1 (Samples 1A-1E). Figures 5A-5EAs shown, the morphology of the porous structure changes with increasing firing temperature. As the temperature increases, the hollow glass microspheres undergo increased softening and opening. It is observed that the surface area decreases with increasing peak firing temperature. Without intending to be bound by any particular theory, it is believed that the increase in softening and opening of the hollow glass microspheres at higher peak firing temperatures causes some of the γ-Al2O3 particles to be surrounded by the glass phase, which is believed to cause the surface area to decrease with increasing peak firing temperature. This is obtained Figure 5D and 5E The support of γ-Al2O3 shows a decrease in the definition between particles, indicating a glassy phase surrounding some γ-Al2O3 particles.

[0181] See now Figure 6 , the XRD patterns of the porous structure of Example 1 (Samples 1A-1E) show the crystalline phase of the porous structure and confirm that the crystalline phase of the porous structure changes with increasing peak firing temperature. At low peak firing temperatures of 820°C and 920°C, the main phases are cristobalite and wollastonite, which are crystalline phases derived from the crystallization of glass from hollow glass microspheres. At lower peak firing temperatures, γ-Al2O3 does not exhibit phase transformation or size change, which results in a larger surface area for Samples 1A and 1B in Table 4. When the temperature increases, an albite crystalline phase is formed, which is a crystalline phase derived from the reaction between the glass of the hollow glass microspheres and γ-Al2O3. In addition, at higher temperatures, the porous structure exhibits XRD peaks characteristic of corundum (α-Al2O3), which is a crystalline phase derived from the transformation of γ-Al2O3. Therefore, it is believed that the change in the crystalline phase with increasing peak firing temperature also contributes to the reduction in surface area with increasing peak firing temperature.

[0182] See now Figure 7 , graphically showing the pore size distribution of each porous structure of Example 1 (Samples 1A-1E). Figure 7 As shown, the pore size distribution has a bimodal pattern, which indicates the presence of nano-sized pores and micro-sized pores. The nano-sized pores are provided by the γ-Al2O3 of the high surface area material, and the micro-sized pores are provided by the hollow glass microspheres. As the peak firing temperature increases from 820°C to 1120°C, the intrusion into the nano-sized pores also decreases, similar to the surface area. Without intending to be limited to any particular theory, it is believed that this reduction in nano-sized pores may originate from an increase in the coverage of the glass relative to the γ-Al2O3 particles, from the formation of albite and corundum crystal phases, or a combination of the two.

[0183] Example 2: Porous structure with coarse inorganic particles (ie, MgO) as secondary phase precursor

[0184] In Example 2, coarse inorganic particles (ie, MgO particles) were used as secondary phase precursors to prepare a porous structure. Table 5 provides the batch composition used to make the porous structure of Example 2. The MgO particles used in Example 2 have a particle size of less than 5 μm. 2 / g of initial surface area. The hollow glass body used in Example 2 is the C100T hollow glass microsphere in Table 3. For Example 2, the hollow glass body, MgO, methylcellulose binder, lubricating oil and water are combined together to produce a batch composition, which is then extruded into a green structure having a honeycomb shape. The green structure is then fired according to the firing process disclosed herein to produce the porous structure of Example 2. For samples 2A-2D, the peak firing temperature varies from 720°C to 920°C. Table 5 provides the porosity and surface area of ​​the porous structure formed by the hollow glass microspheres and MgO particles. Although MgO has a very low initial surface area <5m 2 / g, but it was found that MgO reacted with the hollow glass microspheres to form a new phase with nano-sized pores, which increased the surface area of ​​the porous structure. The best results were obtained with sample 2B, which had a peak firing temperature of 770°C, a porosity of 68%, and a porosity of 2m 2 / g of surface area. Although the surface area is not high (e.g., >5m 2 / g), but the surface area is greater than that of typical cordierite honeycomb porous structures and porous structures made from hollow glass bodies without a secondary phase precursor.

[0185] For comparative purposes, Sample 2E was prepared using a C-100-T hollow glass body without the secondary phase precursor MgO. The porous structure of Sample 2E was fired at a peak firing temperature of 770°C. Table 5 provides the composition, porosity, and surface area of ​​the porous structure of Sample 2E. As shown in Table 5, the porosity of the porous structure of Sample 2E is slightly higher, but the surface area of ​​0.2 is an order of magnitude smaller than the surface area of ​​the porous structure of Sample 2B (which contains MgO and is fired at the same firing temperature of 770°C). Comparing the porous structure of Sample 2B with the porous structure of Sample 2E shows that the presence of the secondary phase precursor can increase the surface area of ​​the porous structure.

[0186] Table 5

[0187]

[0188]

[0189] See now Figures 8A-8D , provides SEM images of the porous structures of samples 2A-2D. Figures 8A-8D As shown, the morphology of the porous structure of samples 2A-2D shows a very porous structure with open pores. Figures 9A-9D, provides SEM images at a higher resolution to show more details of the particle shape in the porous structure of Example 2. Figures 9A-9D As shown, the framework structure of the porous structure is very fine particles.

[0190] See now Fig.10 , the XRD pattern of the porous structure of Example 2 shows the crystalline phase of the porous structure and confirms that the crystalline phase of the porous structure changes as the peak firing temperature increases from 570°C to 920°C. At lower peak firing temperatures below about 720°C or lower, no obvious reaction between MgO and the glass of the hollow glass microspheres is observed, as shown by an XRD pattern showing mainly magnesium oxide (MgO). As the peak firing temperature increases to 720°C and from 720°C to 920°C, new phases of diopside and forsterite are formed, indicating a reaction between MgO and the glass of the hollow glass microspheres.

[0191] See now Fig.11 , graphically showing the pore size distribution of each porous structure of Example 2 (Samples 2A-2D). Fig.11 As shown, the pore size distribution of the porous structure of Example 2 is monomodal with micron-sized pores. In addition, the concentration of micron-sized pores does not change very much as the peak firing temperature increases.

[0192] Example 3: Porous structure with a combination of nano-sized inorganic particles and coarse inorganics as secondary phase precursors

[0193] In Example 3, a combination of nano-sized inorganic particles (i.e., gamma alumina) and coarse inorganic particles (i.e., MgO particles) was used as a secondary phase precursor to prepare a porous structure. Table 6 provides the batch composition used to make the porous structure of Example 2. The gamma alumina (γ-Al2O3) used in Example 3 has a molecular weight of about 230 m 2 / g initial surface area, which can be used to increase the surface area of ​​the substrate. The MgO particles used in Example 3 have an initial surface area of ​​less than 5m 2 For samples 3A-3D, the hollow glass bodies are C100T hollow glass microspheres in Table 3, and for samples 3E-3H, the hollow glass bodies are HN70 hollow glass microspheres in Table 3.

[0194] For Example 3, hollow glass bodies, gamma alumina, MgO, methyl cellulose binder, lubricating oil, and water were combined to produce a batch composition, which was then extruded into a green structure having a honeycomb shape. The green structure was then fired according to the firing process disclosed herein to produce the porous structure of Example 3. The peak firing temperature varied from 720°C to 1020°C for samples 3A-3D, and from 820°C to 1070°C for samples 3E-3H. Table 6 shows the results of the above studies from the simultaneous inclusion of nano-sized inorganic particles (which have a high surface area (e.g., >100 m 2 / g)) and coarse inorganic particles (i.e., with a surface area less than 5 m 2 The combination of gamma alumina and MgO and a firing temperature of less than 1000°C produced samples 3A-3H with high porosity greater than 60% and porous structures greater than 20 m 2 Specifically, for samples 3A-3D containing C100T hollow glass microspheres, 20 vol% MgO, and 15 vol% γ-Al2O3, the best results were obtained at a peak firing temperature of 820°C, which produced a porous structure with a porosity of 63% and a porosity of 23 m 2 For samples 3E-3F containing HN70 hollow glass microspheres, 10 vol% MgO, and 10 vol% γ-Al2O3, the best results were obtained at a peak firing temperature of 920°C, which produced a porous structure with a porosity of 62% and a surface area of ​​25 m 2 / g surface area of ​​the porous structure of sample 3F.

[0195] Table 6

[0196]

[0197]

[0198] See now Figures 12A-12D , SEM images of the porous structures of samples 3A-3D are provided. Fig. 12A As shown, at the peak firing temperature of 720°C, the morphology of the porous structure of sample 3A is not open, and the porosity of the porous structure of sample 3A is low. Fig. 12B and 12C The morphology of samples 3B and 3C (peak firing temperatures of 820°C and 920°C, respectively) shows an open hollow glass body, resulting in increased porosity. Figures 13A-13D , provides SEM images at a higher resolution to show more details of the particle shapes in the porous structure of samples 3A-3D. Figures 13A-13DAs shown, the porous structures of samples 3A-3D show initial γ-Al2O3 particles as well as newly formed nano-sized grains, which combine to produce a high surface area, especially for samples 3A-3C. Fig.13D As shown, when the peak firing temperature increases to 1020 °C, the glass from the hollow glass microspheres covers the initial γ-Al2O3 particles as well as the newly formed nanosized grains, which results in a porous structure of the sample 3D with a thickness of less than 1 μm. 2 / g of reduced surface area.

[0199] See now Figures 14A-14D , provides SEM images of the porous structures of samples 3E-3H. Fig.14A As shown, at the peak firing temperature of 820°C, the morphology of the porous structure of sample 3E is not open, and the porosity of the porous structure of sample 3E is low. Fig. 14B and 14C The morphology of samples 3F and 3G (peak firing temperatures of 920°C and 1020°C, respectively) showed an open hollow glass body, resulting in increased porosity. Figures 15A-15D , SEM images at a higher resolution are provided to show more details of the particle shapes in the porous structure of samples 3E-3H. Figures 15A-15D As shown, the porous structures of samples 3E-3H show initial γ-Al2O3 particles as well as newly formed nano-sized grains, which combine to produce high surface areas, especially for samples 3E-3G. Fig.15D As shown, when the peak firing temperature increases to 1070 °C, the glass from the hollow glass microspheres covers at least a portion of the initial γ-Al2O3 particles as well as the newly formed nanosized grains, which results in a porous structure of about 4 m thick in sample 3H. 2 / g of reduced surface area.

[0200] See now Fig.16, graphically showing the pore size distribution of the porous structure of samples 3A-3D. At a peak firing temperature of 720°C, the pore size distribution of the porous structure of sample 3A exhibits two peaks corresponding to nano-sized pores of γ-alumina and to microporous structures provided by the initial opening of the hollow glass microspheres. When the peak firing temperature is from 820°C (sample 3B) to 1020°C (sample 3D), the pore size distribution is also bimodal, indicating the presence of nano-sized pores and micro-sized pores. The nano-sized pores are provided by the γ-Al2O3 of the high surface area material, and the micro-sized pores are formed by the hollow glass microspheres and MgO. As the peak firing temperature increases from 820°C to 1120°C, the amount of intrusion into the nano-sized pores decreases, which mirrors the decrease in surface area of ​​samples 3B-3D. Without intending to be limited to any particular theory, it is believed that this reduction in nano-sized pores may originate from the glass phase covering an increasing portion of the γ-Al2O3 particles, from the formation of albite and corundum crystalline phases, or a combination of the two.

[0201] See now Fig.17 , graphically showing the pore size distribution of the porous structure of samples 3E-3H. At a peak firing temperature of 820°C, the pore size distribution of sample 3E exhibits three separate peaks corresponding to: nano-sized pores of γ-alumina (<10 nm), pores formed by the initial opening of the hollow glass microspheres (~3000-5000 nm), and microporous structure provided by the interaction between the hollow glass microspheres and MgO (~7000-9000 nm). As the peak firing temperature increases from 920°C (sample 3F) to 1070°C (sample 3H), the amount of intrusion into the nano-sized pores of γ-alumina decreases, mirroring the decrease in surface area of ​​samples 3F-3H. Without intending to be bound by any particular theory, it is believed that this reduction in nano-sized pores may result from the glass phase covering an increasing portion of the γ-Al2O3 particles, from the formation of albite and corundum crystalline phases, or a combination of both. In addition, the size of the peak corresponding to the initial opening of the hollow glass microspheres decreases, and the peak corresponding to the microporous structure generated by the interaction between MgO and the hollow glass microspheres increases. Without being limited to any particular theory, it is believed that the increase in the microporous structure characterized by pore diameters of about 7000 nm to about 9000 nm reflects the increase in the interaction between MgO and the hollow glass microspheres as the temperature increases.

[0202] Example 4-7: CO2 adsorption capacity

[0203] In Examples 4-7, various porous structures were loaded with CO2 adsorbents and then subjected to CO2 adsorption tests. For Example 4, the porous structure had a porosity of 55% and a void volume of less than 0.5 m 2For Example 5, the porous structure is a low surface area porous structure made from hollow glass microspheres without a secondary phase to increase the surface area, and has a porosity of 72% and a pore size of less than 1 m 2 / g specific surface area. For Example 6, the porous structure is a high surface area porous structure including hollow glass microspheres and a secondary phase containing gamma alumina. The porous structure of Example 6 has a porosity of 70% and a surface area of ​​13 m 2 / g specific surface area. For Example 7, the porous structure is a high surface area porous structure, which includes hollow glass microspheres and a secondary phase formed by the reaction of coarse inorganic particles (MgO particles) and the glass of the hollow glass microspheres. The porous structure of Example 7 has a porosity of 66% and a void volume of about 5 m 2 / g specific surface area. Each porous structure of Examples 4-7 has the same honeycomb geometry. Then, each porous structure of Examples 4-7 directly loads a CO2 adsorbent without an intermediate layer to produce a CO2 capture device. The CO2 adsorbent is PEI.

[0204] Then adopt Figure 4 The system 400 shown and described in conjunction with it was used to perform a CO2 adsorption test on each CO2 capture device of Examples 4-7. For the CO2 adsorption test, a cylindrical sample having a porous structure with a diameter of 1 inch (2.54 cm) and a length of 4 inches (10.16 cm) was coated with an adsorbent. The total volume of each sample was 0.0506 liters. Each CO2 adsorption test included an adsorption-desorption cycle. During the desorption process, an air inlet stream containing a CO2 concentration of approximately 450 ppm passed through each sample, and the CO2 concentration of the outlet stream was measured for each sample. The capacity of each sample for CO2 capture is determined by the following equation 1 (EQU.1).

[0205]

[0206] In EQU.1, [CO2] 吸附-入口 is the CO2 concentration in the inlet stream during adsorption, [CO2] 吸附-出口 is the CO2 concentration in the outlet stream during the adsorption process, f is the flow rate through the sample, time is the total time the inlet stream passes through each sample, and V 样品 is the total volume of each sample.

[0207] For the desorption portion of the cycle, each sample was heated to a temperature of 110°C and purged with nitrogen (N2) to release CO2 from the adsorbent. The desorption capacity of each sample to desorb CO2 from the sample was determined using Equation 2 (EQU. 2).

[0208]

[0209] In EQU.1, [CO2] 解吸附-出口 is the CO2 concentration in the outlet stream during desorption, [CO2] 解吸附-入口 is the CO2 concentration in the inlet N2 stream during desorption, f is the flow rate through the sample, time is the total time that N2 gas passes through each sample during desorption, and V 样品 is the total volume of each sample.

[0210] Table 7

[0211]

[0212] As shown in Table 7, they have 13m 2 / g and about 5m 2 The high surface area porous structures of Examples 6 and 7 with a specific surface area of ​​1000 g / g produce greater CO adsorption capacity than the porous structures of Examples 4 and 5 with much lower specific surface areas. Without being limited to any particular theory, it is believed that the high specific surface area of ​​the porous structure can promote the distribution of PEI, which can increase the accessibility of CO gas to the PEI adsorbent. The greater accessibility of CO to the adsorbent in turn increases the adsorption performance of the PEI adsorbent for adsorbing CO.

[0213] It is obvious to those skilled in the art that various modifications and changes can be made to the embodiments described herein without departing from the spirit and scope of the subject matter claimed for protection. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, as long as these modifications and variations fall within the scope of the attached claims and their equivalents.

Claims

1. A porous structure comprising: 5 to 95 weight percent of a hollow glass body, based on the total weight of the porous structure, the hollow glass body comprising silica-containing glass; as well as 5 to 95 weight percent of a secondary phase, based on the total weight of the porous structure, wherein: The hollow glass body and the secondary phase are sintered together; At least a portion of the hollow vitreous body is ruptured; The cavities defined within the individual ruptured hollow vitreous bodies open to each other to form a cavity extending through the porous structure and to the outer surface thereof; The porous structure has a porosity greater than or equal to 50% by volume and a void volume greater than or equal to 5 m 2 / g specific surface area.

2. The porous structure according to claim 1, wherein The specific surface area of ​​the porous structure is greater than or equal to 10m 2 / g or even greater than or equal to 20m 2 / g.

3. The porous structure according to claim 1, wherein The porosity of the porous structure is greater than or equal to 55% or even greater than or equal to 60%.

4. The porous structure according to claim 1, wherein The secondary phases include: With a length greater than or equal to 10m 2 / g of specific surface area of ​​nano-sized inorganic particles; Nanosized grains comprising a reaction product of a reaction between silica-containing glass and coarse inorganic particles, the coarse inorganic particles having a size of less than 10 μm. 2 / g specific surface area and contains an oxide, hydroxide, salt or combination of an alkali metal or an alkaline earth metal; or a combination thereof.

5. The porous structure according to claim 4, wherein The secondary phase includes a phase with a length greater than or equal to 10m 2 / g of nanosized inorganic particles with high specific surface area.

6. The porous structure according to claim 5, wherein Nano-sized inorganic particles have a size greater than or equal to 20 μm. 2 / g, greater than or equal to 50m 2 / g or even greater than or equal to 100m 2 / g specific surface area.

7. The porous structure according to claim 5, wherein Nanosized inorganic particles have a median particle size (d50) of 0.1 nm to 100 nm.

8. The porous structure according to claim 5, wherein: Nano-sized inorganic particles include gamma alumina, zirconia, zeolite, magnesia, silica, CeO2, TiO2, or combinations thereof.

9. The porous structure according to claim 5, wherein: The nano-sized inorganic particles include gamma alumina.

10. The porous structure according to claim 4, wherein The secondary phase includes nano-sized grains that include reaction products of a reaction between the silica-containing glass and the coarse inorganic particles.

11. The porous structure according to claim 10, wherein Coarse inorganic particles have a size less than 10 μm 2 / g specific surface area.

12. The porous structure according to claim 10, wherein The coarse inorganic particles have an average particle size of about 100 nanometers to about 100 microns.

13. The porous structure according to claim 10, wherein The coarse inorganic particles include: MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li2BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or any combination thereof.

14. The porous structure according to claim 10, wherein The coarse inorganic particles include MgO.

15. The porous structure according to claim 10, wherein The secondary phases include: at least one magnesium-based crystalline phase selected from forsterite, clinopyroxene, diopside, or a combination thereof; At least one calcium-based crystalline phase selected from wollastonite, pseudowollastonite, orthorhombic calcite, and cristobalite; or a combination thereof.

16. The porous structure according to claim 4, wherein: Secondary phases include: 2 / g of nano-sized inorganic particles, and nano-sized grains comprising a reaction product of a reaction between silica-containing glass and coarse inorganic particles, the coarse inorganic particles having a size of less than 10 m 2 / g of specific surface area and contains an oxide, hydroxide, salt or a combination thereof of an alkali metal or an alkaline earth metal.

17. The porous structure according to claim 16, wherein The porous structure includes one or more crystalline phases selected from romagnesia, corundum, zirconia, or combinations thereof.

18. The porous structure according to claim 1, wherein The porous structure contains a glassy phase.

19. The porous structure according to claim 1, wherein The plurality of hollow glass bodies include borosilicate glass, soda-lime silicate glass, aluminosilicate glass, alkali aluminosilicate glass, or a combination thereof.

20. The porous structure of claim 1, wherein: The porous structure has a D factor greater than or equal to 0.5, where: The D factor is equal to (d 50 -d 10 ) / d 50 ; d 50 refers to the median pore diameter of the porous structure at which 50 volume % of the open porosity of the porous structure is invaded by mercury during the porosity measurement; and d 10 Equivalent to the pore diameter at which 90% by volume of the open porosity of the porous structure is intruded by mercury during the porosity measurement.

21. The porous structure of claim 1, wherein: The porous structure has a median pore size of 1 μm to 50 μm or 2 μm to 20 μm.

22. The porous structure of claim 1, wherein: The porous structure has a honeycomb shape including a plurality of elongated channels extending through at least a portion of the porous structure, wherein the porous structure has a cell density of less than 400 channels per inch and a mesh thickness of between 2 mils and 8 mils, wherein the cell density refers to the number of elongated channels per square inch of the porous structure cross-section.

23. The porous structure of claim 1, wherein: The porous structure includes a size and shape that is within 15% of the size and shape of the extruded green structure prior to firing to transform the extruded green structure into the porous structure.

24. The porous structure of claim 1, further comprising one or more CO2 sorbents deposited within the cavities of the porous structure.

25. The porous structure of claim 24, wherein: The CO2 adsorbent includes: PEI, MEA, DEA, PPI, PPA, NaOH, Na2CO3, NaHCO3, KOH, K2CO3, KHCO3, or a combination thereof.

26. The porous structure of claim 24, wherein: The CO2 adsorbent is bonded to the surface of the porous structure defining the cavity.

27. The porous structure of claim 24, wherein: The porous structure has no intermediate layer disposed between the surface of the porous structure and the CO2 adsorbent bonded thereto.

28. A CO2 capture method comprising the porous structure of claim 24, wherein: The CO2 capture method includes an adsorption-desorption unit and the porous structure is integrated into the adsorption-desorption unit.

29. A composition for making a ceramic honeycomb, the composition comprising: including a plurality of hollow glass bodies comprising silica glass; A secondary phase precursor comprising: With a length greater than or equal to 10m 2 / g of specific surface area of ​​nano-sized inorganic particles; Coarse inorganic particles having a diameter less than 10 μm 2 / g specific surface area and comprises an oxide, hydroxide, salt or a combination thereof of an alkali metal or an alkaline earth metal; or a combination thereof; a liquid carrier; and Organic system.

30. The composition of claim 29, comprising 50% to 95% by volume of the hollow glass body and 5% to 50% by volume of the secondary phase, wherein: Volume percentages are based on the total bulk volume of the inorganic solid components of the composition.

31. The composition of claim 29, wherein Silica-containing glass includes borosilicate glass, soda-lime silicate glass, aluminosilicate glass, alkali aluminosilicate glass, or a combination thereof.

32. The composition of claim 29, wherein The secondary phase precursor includes nano-sized inorganic particles.

33. The composition of claim 32, wherein Nano-sized inorganic particles have a size greater than or equal to 10 μm. 2 / g specific surface area.

34. The composition of claim 32, wherein The nano-sized inorganic particles include gamma alumina, zirconia, zeolite, magnesia, silica, CeO2, TiO2, or a combination thereof.

35. The composition of claim 29, wherein The secondary phase precursor includes coarse inorganic particles including oxides, hydroxides, salts or combinations thereof of alkali metals or alkaline earth metals.

36. The composition of claim 35, wherein The coarse inorganic particles include: MgO, Mg(OH)2, CaO, Ca(OH)2, Ca3(PO4)2, CaCO3, Li2O, Li2CO3, Li3BO3, Na2O, NaOH, Na2CO3, K2O, KOH, K2CO3, or a combination thereof.

37. The composition of claim 29, wherein The organic system includes one or more of the following: methyl cellulose, CMC, lubricant, PVP, PVA, or a combination thereof.

38. The composition of claim 29, wherein The liquid carrier is: water, one or more alcohols, or a combination thereof.

39. A porous structure prepared using the composition of claim 29.

40. A porous structure, prepared by the following method: Prepare the composition as claimed in claim 29; forming a green structure from the composition; and firing the green structure at a temperature of less than or equal to 1000° C. or even less than or equal to 900° C.; in, The porous structure has a porosity greater than or equal to 50% and a void volume greater than or equal to 5 m 2 / g specific surface area.

41. The porous structure of claim 40, wherein: The porous structure has a size and shape that is within 15% or even within 1% of the size and shape of the green structure prior to firing.

42. The porous structure of claim 40, wherein: The secondary phase precursor includes nano-sized inorganic particles, and firing the green structure bonds the hollow glass microspheres and the nano-sized inorganic particles together and breaks open at least a portion of the hollow glass body to form a porous structure having a porosity greater than or equal to 50% and a void volume greater than or equal to 5 m 2 / g specific surface area.

43. The porous structure of claim 40, wherein: The secondary phase precursor includes coarse inorganic particles comprising an oxide, hydroxide, salt or combination of an alkali metal or alkaline earth metal, and a silica-containing glass that reacts with the hollow glass body to produce nano-sized grains and breaks open at least a portion of the hollow glass body to form a porous structure having a porosity of greater than or equal to 50% and a void volume of greater than or equal to 5 m 2 / g specific surface area.

44. The porous structure of claim 40, wherein: Firing of the green structure includes: raising the green structure to a peak firing temperature of less than or equal to 1000°C; and The green structure is held at the peak firing temperature for a period of time ranging from 1 hour to 10 hours.

45. The porous structure of claim 40, wherein: The porous structure also includes a CO2 sorbent bonded to a surface of a cavity of the porous structure, and the method further includes bonding the CO2 sorbent to the porous structure.

46. ​​The porous structure of claim 40, wherein: Bonding the adsorbent to the porous structure does not include applying an intermediate layer between the surface of the porous structure and the CO2 adsorbent.